RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Iron availability as a time-evolving descriptor linking syntrophic metabolic responses and process performance in nano-iron-amended anaerobic systems - Yujia Ma; Lijing Xue; Zhihong Gao; Chen Chen; Lin Wang; Ming Hua; Zhichao Yang; Chao Shan; Jieshu Qian; Hongchao Li; Weiming Zhang (Bioresource Technology, 2026)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

Scalable MEA electrolyzers for ammonia electrosynthesis at ampere-level current densities - Xiaofang Zhang; Qingzhen Wang; Wen Gan; Kaiwen Yang; Zhijiao Ji; Yunpeng Xue; Shuangen Yu; Yunshan Shang; Junyu Yan; Xiaobo Cheng; Wenshi Li; Zhihua Han; et al. (Chemical Engineering Journal, 2026)

Viscous fragmentation and topology-induced residual gas trapping during gas–water displacement in fracture networks - Kangsheng Xue; Hai Pu; Yanlong Chen; Ming Li; Yu Wu; Lulu Liu; Qingyu Yi; Zheng Ma (Advances in Water Resources, 2026)

Borborobacter xinjiangensis sp. nov., a moderately halophilic bacterium isolated from grapevine rootstock in Xinjiang, China - Xue Li; Yu Tao; Ming Li; Qingzhuang Zhang; Guohong Wu; Jinge Hu; Shijian Bai; Lei Su; Xin Li (Archives of Microbiology, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Hierarchically structured superamphiphobic radiative cooling fabric for personal thermal management - Wen-Jing Zhao; Chao-Hua Xue; Xiao-Jing Guo; Jing-Jing Peng; Li Wan; Yan Yang; Shi-Hang Lv; Jin-Yu Wang; Teng-Xin Wang; Ming-Wei Chang (Chemical Engineering Journal, 2026)

Eco-hydrological processes in controlling vertical and lateral carbon fluxes in a subtropical salt marsh: Insights from modeling and scale-resolved analysis - Ke-Hua Zhu; Li-Shan Tan; Guan-Xun Wang; Li-Ming Xue; Zeng-Feng Li; Hua-Yu Chen; Qing Lyu; Bo-Fei Li; Wei Zhao; Christian Schwarz; Zhen-Ming Ge (CATENA, 2026)

The role of transcription factor MdGeBP3 in Modulating cold stress tolerance and anthocyanin biosynthesis in apple - Ming-Kun Wang; Ran-Xin Liu; Cong-Yu Xu; Yue-Ning Wang; Xiao-Han Qin; Shan-Shan Li; Ying-Xue Lv; Du Liu; Jie Lu; Xiao-Fei Wang (Journal of Plant Physiology, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Robust monitoring design for CO2-flue gas co-storage in saline aquifers under geological heterogeneity - Yuanming Li; Bei Li; Shuangxing Liu; Ming Xue; Xingchun Li; Peng Wu (Process Safety and Environmental Protection, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

SPH numerical analysis of the energy balance during waves interacting with elastic horizontal plate breakwaters - Jia-ming Liang; Xue-yan Li; Yong-kun Chen; Zi-kai Zhou; Zhao-zi Zhang (Ocean Engineering, 2026)

Mining rare earth elements with ammonium sulfate as a leaching agent provokes a significant perturbation in soil microbial function - Yong-He Han; Ming-Zhu Zou; Xue-Mei Wei; Xian Chen; Li-Chao Tong; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Integrating network pharmacology, molecular dynamics, and in vitro assays to unveil the mechanism of costunolide against gastric cancer - Chaohong Zhu; Qiuxiong Chen; Ying Li; Hui Wu; Qijun Ming; Mengyue Ma; Junjie Mu; Xiaoqin Long; Xian Yang; Xue Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Genome-wide analysis of the CHIA gene family and functional characterization of ScCHIA1 under cold and osmotic stress in jojoba (Simmondsia chinensis) - Xue Zhu; Ming Zhu; Luping Li; Ronghao Xia; Huini Xu; Fei Gao; Lamei Zheng (Plant Science, 2026)

Organic matter enrichment and warming synergistically drive sediment phosphorus release in macrophyte-dominated lakes: Geochemical and microbial mechanisms - Fajian Li; Yaobin Lv; Chunmin Zhang; Xue Zhang; Hongbin Yin; Ming Kong (Journal of Cleaner Production, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Metamorphic evolution and geochronology of garnet amphibolite, the Dongbatu tectonic-metamorphic mélange, eastern middle Paleozoic Dunhuang Orogenic Belt, northwest China - Xue-Li Jia; Yichao Chen; Yan-Lin Zhao; Zhen M.G. Li; Hui C.G. Zhang; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Iron oxide-apatite and porphyry Cu–Au deposits controlled by pre-ore degassing, emplacement depths, and evaporite assimilation: A comparative study of the Nihe Fe and Shaxi Cu–Au deposits, Anhui, China - Yi Li; Ke-Zhang Qin; Le Wang; Guo-Xue Song; Tao-Fa Zhou; Yong-Jian Wang; Ming-Guo Zhai (Gondwana Research, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Synergistic effects of sequential ultrasound and autoclaving treatments on the structure, functionality, and digestibility of chestnut starch varieties - Yuan-Yuan Zhang; Can Xu; Ming-Xue Tu; Yin-Ping Zhang; Cong-Hu Li; Liang-Liang Zhu; Ting Hu (Food Chemistry, 2026)

A surface-engineered mycelial biofilm incorporating a self-cascading nanozyme for mycotoxin degradation in edible oils - Xue-ming Cao; Xue-ting Zhu; Yang-yang Geng; Ruo-mu Xia; Jin-min Zhang; Li-na Wu (Chemical Engineering Journal, 2026)

Mechanisms of Hydrating the Lower Stratosphere by Overshooting Convection over the Southern Slopes of the Himalayas - Ming Li; Xue Wu; Daren Lyu; Bing Chen (Advances in Atmospheric Sciences, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Contributions of SARA fractions to asphalt fume composition via experiment and ReaxFF-molecule dynamics - Ming Jia; Hui Li; Xue Zhang; Yu Cheng; Ivan Miguel De Cachinho Cordeiro; A.C.Y. Yuen; Wei Wang; Cheng Wang; Guan Heng Yeoh (Fuel, 2026)

Valorization of Pinus koraiensis nut skin byproducts: Polyphenols alleviate doxorubicin-induced cardiotoxicity via the Nrf2/Keap1-mediated oxidative stress response - Qidong Xue; Kangning Li; Jie Mi; Dekun Cheng; Ruijie Liu; Ming Chang (Food Bioscience, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Optimal production strategies for balancing yield enhancement, carbon sequestration, and soil greenhouse gas flux regulation in Chinese maize systems under straw return and organic fertilizer application - Linli Zhou; Dongping Shen; Keru Wang; Ruizhi Xie; Yuqin Zhang; Bo Ming; Jun Xue; Guoqiang Zhang; Shaokun Li (European Journal of Agronomy, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

The application of Milankovitch cycles in determining provenance direction - Ting-yu Zhang; Hui Xue; Ming-guang Hu; Min-shu Wang; Gen Li; Zhen Lu (Applied Geophysics, 2026)

Distribution pattern and influencing factors of dehydrated sterols: processing degradation of phytosterol - Jie Mi; Mengyuan Zhou; Mingyang Yuan; Qidong Xue; Kangning Li; Ruijie Liu; Ming Chang (Food Chemistry, 2026)

Rapid identification and prediction of the botanical origins and main components of Chinese yam based on a multimodal data fusion of near-infrared spectra and visualization image information - Xue-Qing Fan; Ming-Hui Wei; Li Yang; Mei Xue; Chun-Juan Pu; Jian-Mei Yin; Xi-Chen Yang; Pei-Dong Chen; Gui-Sheng Zhou; Tian-Shu Wang; Hui Yan (Food Chemistry, 2026)

Intelligent ROS-triggered NO and isotretinoin co-delivery hydrogel dressings for microenvironment modulation and rapid repair of diabetic wounds - Bin Lu; Hanzhang Wang; Junyi Zhou; Jieying Lai; Xue Zheng; Shuang-Zhuang Guo; Li-Ming Zhang (Chemical Engineering Journal, 2026)

Quantitative reconstruction of the paleoclimate over the past 200 years in the northern margin of the east Asian summer monsoon, China - Yan-Xia Xue; Hong-Wei Meng; Yu-Zhen Ma; Chao Guo; Ting-Yong Li; Cai-Ming Shen (CATENA, 2026)

The catalytic subunit of cAMP-dependent protein kinase in Taenia solium cysticerci (TsPKA-c): A promising molecular target for the development of novel anti-cysticercosis therapeutics - Li-Qun Wang; Guang-Xue Liu; Pan-Hong Liang; Li Li; Tao-Shan Li; Ai-Ming Guo; Tharheer Oluwashola Amuda; Ke-Ke Wu; Yi-Xuan Wu; Hong Yin; Hong-Bin Yan; Xue-Nong Luo (Veterinary Parasitology, 2026)

Editor's Note to “Wastewater inputs reduce the CO2 uptake by coastal oceans” [Sci. Total Environ., 901 (2023), 165700] - Yunxiao Li; Liang Xue; Xufeng Yang; Ming Xue; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Wei-Jun Cai; Longjun Zhang (Science of The Total Environment, 2026)

Multi-scale investigation into the flaxseed oil emulsions stabilized by soybean protein isolate - (−)-epigallocatechin gallate covalent complexes: An “Interface thickening – Structure unfolding – Antioxidant reinforcement” cascade mechanism - Kangning Li; Qidong Xue; Abdelaziz Elbarbary; Yuxuan Wang; Minjie Cao; Le Yu; Sri Raharjo; Ming Chang; Ruijie Liu (Food Research International, 2026)

Achieving synergistic improvements in maize yield and nitrogen use sustainability through a novel high-density production system enabled by precision stage-specific regulation - Liang Fang; Dongping Shen; Zhen Wang; Linli Zhou; Tingting Zhang; Guoqiang Zhang; Jun Xue; Ruizhi Xie; Peng Hou; Keru Wang; Bo Ming; Ling Gou; et al. (European Journal of Agronomy, 2026)

CCUS technology diffusion and multi-agent investment behavior under policy incentives - Yuanming Li; Bei Li; Shuangxing Liu; Ming Xue; Xingchun Li; Peng Wu (Energy Policy, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Effects of different light intensities on photosynthetic properties of endangered Primula filchnerae seedlings - Ling Wei; Jiali Xue; Jiaxin Quan; Xueyan Zhao; Ming Yue; Qian Li (Photosynthesis Research, 2026)

Enrichment Mechanisms of Rare Earth Elements and Yttrium in the West Philippine Basin Since the Early Pleistocene: Insights from Kernel Principal Component Analysis of Core XT06 Sediments - Yuhan Cao; Huanyu Shi; Yunfeng He; Qiuping Li; Xue Ding; Panfeng Li; Fenglei Gao; Ming Liu; Bangqi Hu (Journal of Ocean University of China, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Electrochemical activation of peroxymonosulfate with a boron-doped diamond anode boosts short-chain fatty acid production from waste activated sludge - Kexin Li; Zhendong Lei; Yujia Zhang; Jinling He; Ming Zheng; Ai Zhang; Pin Gao; Xiang Li; Gang Xue (Water Research, 2026)

Winter CO2 temporal variations in a northern temperate bay: role of biological processes - Hanyang Wang; Hao Qiao; Ming Xin; Faisal Hamzah; Mingrui Li; Yunxiao Li; Qinsheng Wei; Xiangbin Ran; Liang Xue (Marine Environmental Research, 2026)

MdHMGB15 enhances zinc tolerance by activating multiple metal homeostasis genes in apple - Ran-Xin Liu; Ming-kun Wang; Yue-Ning Wang; Xiao-Han Qin; Ying-Xue Lv; Shan-Shan Li; Du Liu; Cong-Yu Xu; Xiao-Fei Wang (Journal of Hazardous Materials, 2026)

Diverse metamorphic P‒T‒t paths of the Mogutai tectono-metamorphic mélange, eastern Paleozoic Dunhuang Orogenic Belt, northwestern China - Yan-Lin Zhao; Yichao Chen; Xue-Li Jia; Hui C.G. Zhang; Zhen M.G. Li; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Advancements in metal-organic frameworks for alkaline oxygen evolution reaction: mechanistic insights, catalyst stability and applications - Ruo-Jin Liu; Xue-Ying Yang; Zheng-Yi Wu; Na Xu; Fu-Li Wang; Ren-Qing Lv; Guanqun Han; Bin Dong; Yong-Ming Chai (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

FE-KFormer: A keypoint-informed transformer model for quantifying the nonlinear cooling effects of urban green space - Yaxing Du; Changhao Zhou; Jiajia Hua; Manrui Xue; Lei Li; Cheuk Ming Mak (Building and Environment, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Reliable Rock Mass Classification for Tunneling: Hole-Level MWD Data Modeling with Cost-Sensitive Bagging - Yue-ming Yuan; Jin-rui Duan; Zhao Han; Yi-guo Xue; Zhi-ping Sun; Fan-meng Kong; Chuan-gui Li (Applied Geophysics, 2026)

First Report on the Asexual Morphology of Nigrograna jinghongensis (Nigrogranaceae, Pleosporales) with a New Host Record from China - Li‐Xue Mi; Hai‐Yan Song; Kevin D. Hyde; Prapassorn D. Eungwanichayapant; Ausana Mapook; Mu‐Sen Chen; Dian‐Ming Hu (New Zealand Journal of Botany, 2026)
Nigrograna jinghongensis was originally described based on sexual morphology from decaying woody litter in Yunnan Province, China. In this study, we report its asexual morph, isolated as endophytes from Tetradium ruticarpum in Anhui Province. The asexual morph of N. jinghongensis features coelomycetous pycnidia that are dark brown and globose to pyriform, bearing filiform, septate conidiophores with phialidic, hyaline conidiogenous cells, and ellipsoidal to subcylindrical, aseptate, guttulate conidia. Species identification was confirmed by multigene phylogenetic analysis using ITS, LSU, SSU, tef1‐α , and rpb2 sequences. This is the first report of the asexual morph of N. jinghongensis , expanding knowledge of its life cycle, ecological adaptability, and host association.

A novel strategy for improving canopy nitrogen density retrieval by deciphering saturation effects and vertical heterogeneity - Hongye Yang; Bo Ming; Chenwei Nie; Dayun Feng; Kexin Gao; Shang Gao; Jun Xue; Guoqiang Zhang; Peng Hou; Ruizhi Xie; Zhenhai Li; Xiuliang Jin; et al. (Computers and Electronics in Agriculture, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

The insect pathogenic fungus Beauveria bassiana excretes a novel effector essential for fungal colonization within the hosts - Kang Wei; Jin-Li Ding; Xue-Ting Wang; Ben-Jie Gao; Ming-Guang Feng; Sheng-Hua Ying (Pesticide Biochemistry and Physiology, 2026)

Human activities and horizontal gene transfer shape the resistome landscapes of non-human primates - Yue Sun; Mingyi Zhang; Yang Teng; Yueqi Yin; Jingcheng Ran; Haijun Su; Hongjia Li; Xiaolong Huang; Zexu Long; Xue Sun; Huijuan Pan; Xiaochen Wang; et al. (Journal of Hazardous Materials, 2026)

Multiple resonance thermally activated delayed fluorescence emitters containing novel S-based acceptor with narrowed FWHM and enhanced EQE - Xiao-Xue Xia; Guo Yuan; Feng-Ming Xie; Qiang Zhang; Yan-Qing Li; Ze Hua; Jian-Xin Tang; Xin Zhao (Chemical Engineering Journal, 2026)

Historical influences of climate, vegetation and soil erosion on primary productivity of Huguangyan Maar Lake, southern China, documented by sedimentary phosphorus fractions for the past 1400 years - Hongpan Xue; Yiyan Chen; Xin Zhou; Luyao Tu; Li Ma; Shiwei Jiang; Ming Ji; Chao Huang; Deming Kong; Yanan Shen (CATENA, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Strategic 1,n-migration of boronate complexes: a novel platform for remote C–C bond construction - Yi-Ming Chen; Xue Li; Zhi-Gang Xu (Molecular Diversity, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Complex terrain causes global model prediction biases of 21.7 Zhengzhou extreme precipitation - Peng Wei; Xin Xu; Ming Xue; Jian Li; Kun Zhao; Qinghong Zhang (Science Bulletin, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

Calcium-phosphate mediated green remediation of uranium mine water: sulfur-fixing ash enhanced phosphorus leaching from phosphogypsum for targeted uranium mineralization - Xue Xia; Ming Guo; Dan Chen; Yinyin Peng; Jialin Li; E. Li; Chunyan Ma; Xiaoqin Nie; Faqin Dong (Journal of Water Process Engineering, 2026)

Methane emissions from global shallow lakes: Patterns, key drivers, and mitigation strategies - Rongwei Xiong; Yong Li; Ming Chen; Jinquan Huang; Yan Xue (Journal of Cleaner Production, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Copper mediates oxidative stress and immune response in snakehead (Channa argus) through Nrf2 and NF-κB pathway - Xue-qin Wu; Ming-ze Li; Lu Lu; Xiu-mei Chen; Xiao-tian Niu; Yi-di Kong; Gui-qin Wang; Chang-ge Xia; Min Li (Fish & Shellfish Immunology, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Corrigendum to “Dendrobium officinale polysaccharide promotes M1 polarization of TAMs to inhibit tumor growth by targeting TLR2” [Carbohydrate Polymers 292 (2022) 119683] - Hong-Yan Wang; Ji-Chun Ge; Feng-Yun Zhang; Xue-Qiang Zha; Jian Liu; Qiang-Ming Li; Jian-Ping Luo (Carbohydrate Polymers, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Rapid electrochemical fabrication of MOF-coated mesh membranes with complementary wettability for high-efficiency oil-water separation - Yi-Le Chen; Wei Shao; Xiao-Feng Zhong; Si-Yuan Yang; Zi-Meng Xu; Jia-Jun Sun; Gang-Jun Chen; Pan-Pan Zhang; Yi Li; Ming Xue (Journal of Hazardous Materials, 2025)

Optimizing molecular distillation film scraper by CFD and experiment: VE extraction from SODD - Mengyuan Zhou; Ziwei Yu; Qidong Xue; Peng Zhang; Zhengzhang Wu; Jie Mi; Kangning Li; Mingyang Yuan; Ruijie Liu; Ming Chang (Innovative Food Science & Emerging Technologies, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Non-destructive bio-fabrication of gadolinium oxide-encapsulated exosomes via bioreactor culture for enhanced MR angiography with efficient renal clearance - Xianglong Zhao; Yan Wang; Ziyue Zhang; Xue Li; Ming Dong (Chemical Engineering Journal, 2025)

An innovative intimately coupled photocatalysis and biodegradation system for simultaneous removal of emerging contaminants and nitrate - Shi-Ming Niu; Thangavel Sangeetha; Xue-Dong Zhang; Wei-Mon Yan; Peng-Fei Li; Jiří Ryšavý; Jakub Čespiva; Min-Hua Cui (Chemical Engineering Journal, 2025)

Pan-genomic insights into RLK family evolution and adaptation in Dioscorea alata - Zhi-Yan Wei; Sai-Xi Li; Ming-Han Li; Jie Tang; Yu-Qian Jiang; Xin-Yu Lu; Yan-Mei Zhang; Jia-Yu Xue (Plant Molecular Biology, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Conditional QTL/QTN mapping for seed width and mining candidate genes based on soybean FW-RIL population - Xu Wang; Bo Hu; Hong Xue; Ming Yuan; Quanzhong Dong; Wen-Xia Li; Zhimin Dong; Hailong Ning (Molecular Genetics and Genomics, 2025)

Study on the mechanism of costunolide inhibiting triple-negative breast cancer by EGFR ubiquitination and degradation to suppress the ERK/AKT signaling pathway - Ying Li; Junjie Mu; Qiuxiong Chen; Qian Ming; Chaohong Zhu; Yujie Xiao; Baoli Qiu; Xue Zhang; Baoshun Zhang; Xian Yang (Journal of Molecular Histology, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

Erratum to: Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

An integrated multi-algorithm analysis to decipher senescence and metabolic characteristics in nucleus pulposus cells during disc degeneration - Zhuangyao Liao; Ming Li; Ziyu Chen; Zhi Yao; Yuluan Wu; Zhen Tan; Junyu Qian; Chunyuan Yang; Lin Huang; Lixiang Xue; Deli Wang (GeroScience, 2025)
Accumulating evidence has suggested that intervertebral disc degeneration (IVDD) serves as a health problem deserving attention from worldwide, owing to the low back pain and even disability it causes. Cellular senescence, an irreversible process of terminal cell cycle arrest, plays an essential role in the degeneration of nucleus pulposus (NP) cells and IVDD with an unknown underlying mechanism. Here, we have explored the senescence signature in IVDD through high dimensional weighted gene co-expression network analysis (hdWGCNA) algorithm in two single cell datasets (PRJCA014236 and GSE244889) to construct a novel signature called NP_Senescence, which accurately identifies the patients with IVDD. The efficacy and accuracy were validated in various external datasets, including two expression array datasets (GSE70362 and GSE34095) and one single cell dataset (GSE230809). Additionally, the accuracy of the specific model was also verified with the senescent cell identification (SenCID) algorithm. IVDD patients with a high NP_Senescence score exhibited the characteristics of compensated activation of hyaluronic acid monomers synthesis and abnormal status of DNA damage repair through single-cell Flux Estimation Analysis (scFEA) algorithm. Furthermore, the NP_Senescence was negatively associated with the level of AMP and Glucose-1-phosphate, while positively associated with the level of β-alanine and UDP-glucuronic acid. In conclusion, we constructed a novel disc-specific scoring model NP_Senescence by comprehensively analyzing the senescence-related genes of IVDD, which can be used for patient early diagnosis and treatment, as well as the identification of metabolic characteristics.

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Surface-modified nanoplastics facilitate the dissemination and persistence of antibiotic resistance genes - Xiaojie Sun; Xue Chen; Jie Ming; Zhiquan Lin; Yue-Zhong Li; Bing-Jie Ni; Shou-Qing Ni (Journal of Hazardous Materials, 2025)

Scale- and age-dependent climate response patterns revealed in Pinus sylvestris var. mongolica and Larix principis-rupprechtii plantations in northern China - Qian-Nan Leng; Xue-Wei Gong; Ming-Yong Li; Han Shi; Zhao-Kui Li; Guang-You Hao (Forest Ecology and Management, 2025)

Development of chondroitin sulfate-modified quinoa protein isolate-dihydromyricetin composite nanoparticles: Focus on naringenin delivery, cell cytoprotective ability and anti-inflammatory effects - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Behaviour of lunar regolith simulant geopolymer-filled aluminium alloy circular hollow section and square hollow section stub columns - Shuai Li; Xuanyi Xue; Jianghuai Zhan; Tak-Ming Chan; Ben Young (Engineering Structures, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Positively correlated singlet and triplet hybridization governed by excited-state energy alignment in organic photovoltaics - Yue Ren; Li-Yuan Peng; Hou Tong; Ming-Yang Li; Xue Wu; Guang-Yan Sun (Chemical Engineering Journal, 2025)

Potential of non-digestible polysaccharides as GLP-1 secretagogues: action mechanisms, structure-activity relationships and clinical applications - Zhen-Zi Shang; Hui-Yu Ye; Qiang-Ming Li; Xue-Qiang Zha; Jian-Ping Luo (Carbohydrate Polymers, 2025)

Revisiting the genesis of Bi-Te-Au-S associations: Implications for the ore-forming processes in gold deposits - Gao-Hua Fan; Jian-Wei Li; Zhan-Ke Li; Xue-Feng Yu; Xiao-Dong Deng; Jin-Hao Liu; Hang-Jin Jiang; Hong-Jun Sun; Tian-Ming Zhang (Chemical Geology, 2025)

Transplanting Cetobacterium can alleviate acute ammonia intoxication by promoting the synthesis of ornithine of yellow catfish - Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Aquaculture, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Geochemistry of trace elements of pyrite and its implications in intermediate sulfidation epithermal systems: Case study based on the Zhengguang Au–Zn deposit, North-East China - Zhang-Wei Qin; Le Wang; Ke-Zhang Qin; Guang-Ming Li; Sheng-Chao Xue; Guo-Xue Song (Journal of Geochemical Exploration, 2025)

Effect of Zn/Fe dual-modification on the adsorption and advanced oxidation properties of Jerusalem artichoke stalk biochar - Jiacheng Li; Ming Zhang; Lijun Wu; Gaigai Xue; Jian Liu; Peiyong Ma; Lu Wang (Journal of Environmental Chemical Engineering, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Unraveling the applicability and thermal performance of PCM-impregnated wood in personalized comfort systems: Thermal manikin verification - Xiujie Li; Cheuk Ming Mak; Peng Xue; Rong Xue; Hai Ming Wong (Energy and Buildings, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Jian Zhang; Ming-Qiang Liang; Jun-Yun Li; Yao Wu; Yan-Xia Xue; Wen-Jun Sun; Xiang-Zhuo Liu; Jin-Ke Chen; Chao-Jun Chen; Ting-Yong Li (Quaternary Science Reviews, 2025)

Made in China 2025: Artificial intelligence intervention and urban green economy development - Malin Song; Ming Yu; Xue-Li Chen; Oana-Ramona Lobonț; Juntao Du (Journal of Environmental Management, 2025)

Petrological and thermodynamic constraints on carbonate stability in altered oceanic crust subducted to subarc depths: Insights from carbonate-bearing eclogites in the Western Alps - Zeng-Li Guo; Jin-Xue Du; Li-Fei Zhang; Thomas Bader; Ren-Biao Tao; Ze-Ming Zhang; Kurt Bucher; Ting-Nan Gong; Jin-Hong Yu (Geochimica et Cosmochimica Acta, 2025)

The effect of ligand regulation on mechanism of alkaline oxygen evolution reaction under industrial scale - Xin-Ru Li; Xue-Jun Zhai; Hao-Zheng Liu; Xin Wen; Yanbin Qi; Chen Zhang; Guodong Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Organophosphate esters and their transformation products in megacity atmospheres: Size-dependent gas-particle partitioning and transformation potential - Chun-Xue Tang; Min-Qi Tang; Chen-Chou Wu; Cheng Li; Ming-Hong Cai; Lian-Jun Bao; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Corrigendum to “Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties” [Food Chemistry 481 (2025) 1–11 144089] - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Corrigendum to “Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations” [Comput. Geotech. 182 (2025) 107160] - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Low electronegativity bimetallic doping modulates electrocatalytic nitrogen reduction reaction pathways for synergistic multi-objective optimization - Zhijiao Ji; Xiaofang Zhang; Wen Gan; Yunpeng Xue; Xuelei Duan; Zhe Zhou; Zhihua Han; Shuai Zhao; Bo Feng; Chufu Li; Ming Xu; Guangli He (Chemical Engineering Journal, 2025)

Spatial and temporal characteristics of vegetation resilience to drought in China - Mengyuan Wei; Liang Jiao; Peng Zhang; Ruhong Xue; Xuge Wang; Qian Li; Ming Jin (Science China Earth Sciences, 2025)

Chronic and Intergenerational Toxicity of Chloramine-T in Moina macrocopa Following Prolonged Exposure - Xue Lei Hu; Sui Jun Cai; Ming Chen; Le Yi Lin; Jin Lan Peng; Jin Ling Liu; Yun Hui Li; Lu Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Freezing-enhanced degradation of naproxen by bicarbonate activated hydrogen peroxide: Peformance and mechanisms - Genbao Zhang; Yunze Zhao; Yihang Guo; Ming Li; Qingling Meng; Baoling Yuan; Honghai Xue; Hongliang Wang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Administration of Cetobacterium somerae ceto isolated from the intestine of yellow catfish (Pelteobagrus fulvidraco) as potential probiotics against chronic ammonia stress - Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Aquaculture, 2025)

Chermesins I-N: Bioactive spiromeroterpenoids from the marine-sourced fungus Penicillium chermesinum AS-400 - Yi-Wei Liu; Xue-Yi Hu; Xiao-Dan Chen; Xiao-Ming Li; Sui-Qun Yang; Hong-Lei Li; Bin-Gui Wang (Phytochemistry, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Asphalt pavement emission behavior under solar radiation during in-service period - Ming Jia; Hui Li; Xue Zhang; Ivan Miguel De Cachinho Cordeiro; Lin Bo; Guan Heng Yeoh (Journal of Hazardous Materials, 2025)

Preparation and application of bioadhesive hydrogel powder loaded with quorum sensing inhibitor isomaltitol for salmon preservation - Ke Liu; Ming Zhang; Wutong Bai; Wenjing Yang; Xinran Lv; Xue Bai; Xuepeng Li; Defu Zhang; Jianrong Li (Food and Bioproducts Processing, 2025)

Investigation on effects of TiO2 on cucumber seedlings using ICP-OES and LA-ICP-MS - Yu Wang; Qi Liu; Zhen Shao; Xue-Sheng Wang; Ya-Fei Chen; Jun-Jie Bai; Ming-Li Chen; Jian-Hua Wang (Analytica Chimica Acta, 2025)

Amino-modified IONPs potentiates ferroptotic cell death due to the release of Fe ion in the lysosome - Zijuan Qi; Xiaofeng Huang; Jiajun Jing; Wenya Feng; Ming Xu; Li Yan; Ming Gao; Sijin Liu; Xue-Feng Yu (Journal of Environmental Sciences, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

Fucoxanthin promotes the conversion efficiency of alpha-linolenic acid in feeding to docosahexaenoic acid in quail egg yolk - Wen-Lei Guo; Shuai-Shuai Fu; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Yu-Ming Wang; Tian-Tian Zhang (Food Chemistry, 2025)

Optimization of enzymatic hydrolysis of collagen and screening and application of hypolipidemic peptide - Yancheng Bi; Ming Zhang; Ke Liu; Xinran Lv; Xuepeng Li; Xue Gao; Fangchao Cui; Defu Zhang; Jianrong Li (Food Bioscience, 2025)

Ornithinibacillus xuwenensis sp. nov., A Novel Thermotolerant Bacterium Isolated from Mangrove Sediment - Ming Li; Xixi Hu; Yuan Ni; Tiancheng Ni; Feng Li; Dong Xue (Current Microbiology, 2025)

Extensive cytonuclear discordance revealed by phylogenomic analyses suggests complex evolutionary history in the holly genus Ilex (Aquifoliaceae) - Ke-Wang Xu; Yi Yang; Hong Chen; Chen-Xue Lin; Lei Jiang; Zhong-Long Guo; Meng Li; Ming-Zhuo Hao; Kai-Kai Meng (Molecular Phylogenetics and Evolution, 2025)

Dual–mode strategy for the determination of vanillin in milk–based products based on molecular-imprinted nanozymes - Can Zhang; Yongfei Zhou; Li Ming; Lihong Chen; Minqiao Xue; Jing Zhang; Hongyan Zhang (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Flexible Ag/AgCl quasi-reference electrode with nano silver dendrites semi-embedded in PDMS: Ensuring long operation lifespan, remarkable stability for electrophysiological monitoring and flexible sensor applications - Jing Sun; Yalei Mei; Weiliang Bai; Li Han; Yuqiang Li; Yuzhong Gao; Ming-Fei Lang; Hongsheng Xue (Chemical Engineering Journal, 2025)

Strategic regulation of crystallization kinetics to achieve efficient pure-red quasi-2D perovskite light-emitting diodes - Yunhui Kuang; Yazhuo Xue; Zheng Zhang; Lvpeng Yang; Tong Bie; Rui Li; Wenxi Liang; Naigen Zhou; Ming Shao (Chemical Engineering Journal, 2025)

Remodeling of bacterial nitrilase active pocket improves the capability to degrade glucosinolate-derived nitriles - Ming-Yu Liu; Yu-Yue Wang; Han-Zhi Li; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (World Journal of Microbiology and Biotechnology, 2025)

Roles of ecological and hydrological processes in the variability of carbon fluxes in a salt marsh of the Yangtze Estuary: Model simulations vs. measurements - Ke-Hua Zhu; Zeng-Feng Li; Wei Zhao; Li-Ming Xue; Hua-Yu Chen; Qing Lyu; Shi-Xian Liu; Zhen-Ming Ge (Agricultural and Forest Meteorology, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

A comprehensive analysis of metabolomics and transcriptomics revealed the mTOR-autophagy pathway is involved in ammonia metabolism of yellow catfish Pelteobagrus fulvidraco - Muzi Zhang; Shidong Wang; Xue Li; Ming Li (Aquaculture, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Warming effects on the emission pathways of N2O and CH4 and the role of water column in shallow eutrophic lakes - Rongwei Xiong; Ming Chen; Yong Li; Guangbao Sun; Jinquan Huang; Yan Xue; Zeyuan Shan; Tianqi Li (Science of The Total Environment, 2025)

Treatment of dye-containing wastewater using discarded animal blood-derived hemoglobin crystals - Xiao-Qian Jin; Jie Liu; Chen-Yuan Li; Liang-Liang Chen; Jia-Lei Li; Xue-Ting Wang; Guang-Ming Mi; Da-Chuan Yin (Journal of Environmental Management, 2025)

A super convenient and specific CRISPR/Cas12a diagnostic platform for toxigenic Burkholderia gladioli based on virulence genes - Yu Xie; Li Liu; Xue-Ming Cao; Zuo-Qi Gai; Xu Zhang; Hong-Tao Lei; Zhen-Lin Xu; Xing Shen (Food Control, 2025)

Structurally resilient carbon nanofiber aerogels from aramid nanofibers for thermal insulation under extreme conditions - Jintao Zhou; Enjie Wu; Yinghe Hu; Ming Jiang; Chang Liu; Luyun Xue; Heyi Li; Yuanjun Liu; Xupin Zhuang (Chemical Engineering Journal, 2025)

Synthesis, molecular docking studies of formononetin derivatives as potent Bax agonists for anticancer activity - Wei-Dong Jia; Xue Bai; Qian-Qian Ma; Ming Bian; Chun-Mei Bai; Di Li; Li-Fei Li; Cheng-xi Wei; Li-Jun Yu (Natural Product Research, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Activation autophagy enhances ammonia detoxification by boosting urea and glutamine synthesis in yellow catfish (Pelteobagrus fulvidraco) - Muzi Zhang; Shidong Wang; Xue Li; Ming Li (Aquaculture, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Transparent exopolymer particles (TEP) research: From the ocean to water treatment - Ming Li; Xiang Jia; Wei Fan; Na Li; Honghai Xue; Lei Wu; Chen Lyu; Mengnan Shen (Journal of Environmental Management, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Dynamics of high-yielding maize genotypes under intensive management across multiple environments - Rongfa Li; Guoqiang Zhang; Ruizhi Xie; Peng Hou; Bo Ming; Jun Xue; Keru Wang; Shaokun Li (European Journal of Agronomy, 2025)

Zr4+-doped PVA-based fiber films: Enhanced mechanical properties, degradability, and applications in green energy - Song Xue; Wenjing Qin; Changshun Gu; Mengyao Chen; Hanlin Zhai; Xiangchuan Zhao; Xinxin Li; Yanli Wang; Le Ge; Shengrong Li; Yixin Xu; Zeyu Ming; et al. (Chemical Engineering Journal, 2025)

The analysis of the genetic loci affecting phenotypic plasticity of soybean isoflavone content by dQTG.seq model - Zhenhong Yang; Yuhang Zhan; Yina Zhu; Hanhan Zhu; Changjun Zhou; Ming Yuan; Haiyan Li; Miao Liu; Weili Teng; Yongguang Li; Xue Zhao; Yuhe Wang; et al. (Theoretical and Applied Genetics, 2025)

Palaeowind reconstruction from Lower Cretaceous wave-dominated depositional records of the Tanan Depression, Northeast Asia - Xinyu Xue; Zaixing Jiang; Chao Liu; Li Wang; Huanyu Xie; Lizhou Song; Ming Su (Journal of Oceanology and Limnology, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Comparative genomic analyses of the genus Robertmurraya and proposal of the novel species Robertmurraya mangrovi sp. nov., isolated from mangrove soil - Ming Li; Xixi Hu; Tiancheng Ni; Yuan Ni; Dong Xue; Feng Li (Antonie van Leeuwenhoek, 2025)

Dietary Iodine Can Effectively Alleviate the Adverse Effects of Fermented Rapeseed Meal on the Growth, Liver Health, and Antioxidant Capacity of Tilapia (GIFT, Oreochromis niloticus) - Di Peng; Ya-Xue Li; Li-Xue Dong; Ke Cheng; Hua Wen; Juan Tian; Jian-Min Zhang; Yang-Yang Liu; Wei-Hua Gao; Yong Min; Ming-Dian Liu; Ming Jiang (Fishes, 2024)
An 8-week feeding trial was conducted to evaluate the effects of dietary fermented rapeseed meal (FRM), potassium iodide, and their interactions on growth performance, approximate composition, and antioxidant capacity in tilapia, Oreochromis niloticus (initial body weight: 3.50 ± 0.15 g). Six isonitrogenous and isolipidic diets from a 2 × 3 factorial design were formulated with two levels of FRM (25.8 and 51.6%) and three levels of potassium iodide (0, 6, and 12 mg/kg), respectively. The results indicated that dietary levels of FRM and iodine had no significant influence on the SR of tilapia but exerted significant effects on weight gain (WG), specific growth rate (SGR), feed intake (FI), hepatosomatic index, and viscerosomatic index. The WG, SGR, and FI of tilapia in the 51.6% FRM groups were significantly lower than those in other groups (p

Research progress on iron-rich industrial waste as environmentally functional material - Xue Sun; Chenglei Hu; Tianguo Li; Jilai Zhang; Youbo Su; Ming Jiang (Sustainable Chemistry and Pharmacy, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Dendrobium huoshanense stem polysaccharide exhibits gastroprotective effect via regulating PI3K/AKT, NF-κB and Nrf-2 signaling in high-salt diet-induced gastritis mice - Hui-Yu Ye; Zhen-Zi Shang; Xin Gao; Xue-Qiang Zha; Feng-Yun Zhang; Qiang-Ming Li; Jian Liu; Jian-Ping Luo (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Laboratorial investigation on optical, thermal and pavement performance of biomimetic dark reflective coatings with composite structure for pavement cooling - Xue Zhang; Hui Li; Ming Jia; Ning Xie; Ioannis Kousis; Mattheos Santamouris (Building and Environment, 2024)

A self-supervised missing trace interpolation framework for seismic data reconstruction - Ming Li; Xue-song Yan; Cheng-yu Hu (Earth Science Informatics, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Clostridium lamae sp. nov., a novel bacterium isolated from the fresh feces of alpaca - Xue Li; Ming Li; Weixiong Shi; Xia Li; Zhiguang Xiang; Lei Su (Antonie van Leeuwenhoek, 2024)

Ellagic acid can mitigate chronic ammonia stress-induced adverse effects through the augmentation of liver autophagy in yellow catfish (Pelteobagrus fulvidraco) - Shidong Wang; Xue Li; Muzi Zhang; Haibo Jiang; Yunxia Qian; Ming Li (Aquaculture, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Research on simulation model of deepwater drilling and optimization method of drilling parameters based on energy - Ming Xiang; Bin Li; Yingming He; Zhiqiang Lin; Weiguo Hai; Jin Wang; Qilong Xue (Ocean Engineering, 2024)

Hydro-morphology and water quality jointly shape the structure and network stability of the plankton community in multi-tributary river basins - Chao Chang; En Hu; Xudong Xue; Juan Li; Dou Du; Fang Yang; Ming Li (Journal of Hydrology, 2024)

Sustainable protein/polysaccharide aerogel for the simultaneous and efficient removal of multiple organic contaminants: Insights from DFT calculations and phenomenological mass–transfer modeling - Ming-Xing Li; Yan-Shu Xiong; Qi-Qi Huang; Yi-Wen Luo; Wei Wei; Hai-Qin Lu; Fang-Xue Hang; Wen Li; Fujie Liu; Kai Li (Journal of Hazardous Materials, 2024)

Dual decoration of quinoa protein isolate by different dietary polyphenols with covalent and noncovalent approaches: Structure characterization, conformational changes and functional properties - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Hydrocolloids, 2024)

CDKN1A promotes Cis-induced AKI by inducing cytoplasmic ROS production and ferroptosis - Qian Gao; Jun-ming Chen; Chen-sui-zi Li; Jia-yi Zhan; Xue-dong Yin; Ben-shang Li; Hong-liang Dong; Lian-xiang Luo; Zhi-ling Li (Food and Chemical Toxicology, 2024)

Advancing the frontiers of CO2 geological storage: A statistical and computational perspective - Ming Li; Xue Zhou; Congguang Zhang; Zhi Zhang; Tianfei Yu (Earth-Science Reviews, 2024)

Understanding Simulated Causes of Damaging Surface Winds in a Derecho-Producing Mesoscale Convective System near the East China Coast Based on Convection-Permitting Simulations - Liping Luo; Ming Xue; Xin Xu; Lijuan Li; Qiang Zhang; Ziqi Fan (Advances in Atmospheric Sciences, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Sesquiterpene lactones from Tithonia diversifolia with ferroptosis-inducing activities - Ao-Xue Ding; Yi-Ming Shan; Chen-Yue Li; Guo-Qing Qin; Tong Chen; Qing Wang; Xiang-Gang Hu; Peng-Ju Guo; Hai-Jun Yu; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry, 2024)

Experimental investigation on suppression effect of molecular sieve powders on asphalt fume - Ming Jia; Hui Li; Xue Zhang; Yuzhao Han; Ivan Miguel De Cachinho Cordeiro; Guan Heng Yeoh (Journal of Cleaner Production, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

A wearable electrochemical sensor for the monitoring of neonicotinoid insecticides, salicylic acid and the pH in plant guttation - Guanglei Chu; Siping Yu; Yuhang Wang; Weifeng Zhang; Bing Xue; Jinqi Huang; Zhiwei Wang; Jianghe Luo; Xia Sun; Ming Li (Chemical Engineering Journal, 2024)

Sesquiterpenes from Tinospora sinensis and their chemotaxonomic significance - Rui Ao; Ming-Hui Li; Zi-Nan Xiao; Xue-Lian Tang; Jun-Sheng Zhang; Hua Zhang (Biochemical Systematics and Ecology, 2024)

Transcription factor NecR promotes the synthesis of neomycin in Streptomyces fradiae - Yihan Cheng; Rumeng Han; Jun Liu; Yan Liu; Kun Liu; Ming Zhao; Ruihua Liu; Weiquan Li; Xiangfei Li; Zhenglian Xue (Systems Microbiology and Biomanufacturing, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

Identification of systemic nitrogen signaling in foxtail millet (Setaria italica) roots based on split-root system and transcriptome analysis - Xin-Li Yao; Yu-Ze Wang; Hui-Xin Meng; Ming-Hua Zhang; Xuan Zhou; Xue-Ting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; et al. (Plant Cell Reports, 2024)

Enhancing CO2 storage and marine carbon sink based on seawater mineral carbonation - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Shuo Chen Li; Zhi Bo Wang; Jun Ma (Marine Pollution Bulletin, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Three undescribed coumarins from the roots of Angelica pubescens - Fuyong Ni; Xue Xie; Xue Huai; Xiao Yu; Hongda Zhang; Ming Li; Jianhui Wen; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Wei Xiao (Natural Product Research, 2024)

Dietary chitosan reversed the toxic effects of polystyrene microplastics on Nile tilapia (Oreochromis niloticus) liver by inhibiting mitochondrial damage - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Hua Wen; Shan Zhong; Yun-feng Li; Ming Jiang (Reviews in Fish Biology and Fisheries, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

miR-199-5p mediates the regulation of autophagy by targeting mTOR signaling and involvement in ammonia detoxification under ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Shidong Wang; Xue Li; Muzi Zhang; Yunxia Qian; Erchao Li; Xiaohua Teng; Ming Li (Aquaculture, 2024)

Pristimerin exhibits anti-cancer activity by inducing ER stress and AKT/GSK3β pathway through increasing intracellular ROS production in human esophageal cancer cells - Wei-Bin Hu; Yi-Ting Liu; Jing Li; Ying Wang; Xuan-Zi Sun; Ming-Yu Hua; Xue-Ting Liu; Bei-Na Hui (Toxicology in Vitro, 2024)

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Impact of wildfire ash on skin and gut microbiomes and survival of Rana dybowskii - Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xue-wen Yang; Xiao-yun Han; Li-yong Cui; Qing Tong (Journal of Hazardous Materials, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Co-assembly of quinoa protein isolate and shellac as nano-vehicles for naringenin: Characterization, formation mechanism, release behavior and cellular uptake - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

A diffusion model-based framework USDDM for random noise elimination of seismic signal - Ming Li; Xue-song Yan; Cheng-yu Hu (Earth Science Informatics, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Biochar produced from diverse invasive species improves remediation of cadmium-contaminated soils - Xue Wang; Wei-Long Zheng; Hao-Ming Yuan; Mark van Kleunen; Fei-Hai Yu; Mai-He Li (Biological Invasions, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Impact of antibiotic therapy on cutaneous and gut microbiota in Rana dybowskii amphibians: Insights and implications - Xin-zhou Long; Wen-jing Dong; Ming-da Xu; Xue-dong Han; Xiao-yun Han; Li-yong Cui; Qing Tong (Aquaculture, 2024)

Recovering carbon fibers from waste CFRPs via pyrolysis-oxidation method: Implications for reuse in remanufactured materials - Ming-xin Xu; Xiang-xi Meng; Qi-si Li; Wei-wei Chen; Hong-ji Xue; Hao Jiang; Hai-wen Ji; Qiang Lu (Waste Management, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Highly salt-resistant polypyrrole decorated waste mop sponge solar evaporator for efficient desalination - Zhihui Yang; Chenxi Han; Yue Zheng; Yibing Chen; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Desalination, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Toxic effect and mRNA mechanism of moon dust simulant induced pulmonary inflammation in rats - Jintao Wang; Yuan Xue; Bin Wu; Ming Lei; Honglei Ma; Xinxing He; Qi Tan; Jian Guan; Wei Song; Renfu Li; Xinguang Cui (Toxicology, 2024)

Metabolites assay offers potential solution to improve the rooster semen cryopreservation - Xue Du; Yuanning Zhang; Duoxi Li; Jie Han; Yali Liu; Lijuan Bai; Tao Huang; Ming Cui; Panlin Wang; Xianzhong Zheng; Ayong Zhao (Theriogenology, 2024)

Enhancement of autophagy can alleviate oxidative stress, inflammation, and apoptosis induced by ammonia stress in yellow catfish Pelteobagrus fulvidraco - Xue Li; Shidong Wang; Muzi Zhang; Ming Li (Fish & Shellfish Immunology, 2024)

Flexible human-machine interface touch system based on double-network solid-state ionic conductive elastomers - Wang Zhan; Qi Zhang; Zhilu Ye; Yuhao Wang; Zihao Yang; Yijing Wang; Cuiling Zhang; Zeying Zhang; Li Xue; Feng Ma; Zhiguang Wang; Niancai Peng; et al. (Chemical Engineering Journal, 2024)

Ferroptosis: a critical mechanism of N6-methyladenosine modification involved in carcinogenesis and tumor progression - Qingqing Wei; Changning Xue; Mengna Li; Jianxia Wei; Lemei Zheng; Shipeng Chen; Yumei Duan; Hongyu Deng; Faqing Tang; Wei Xiong; Ming Zhou (Science China Life Sciences, 2024)

The magmatic origin of propylitic alteration of the Zhengguang epithermal Au-Zn deposit, Heilongjiang, China: evidence from mineral compositions and H–O-Sr isotopes - Le Wang; Ming-Jian Cao; Shen Gao; Massimo Chiaradia; Pete Hollings; Ke-Zhang Qin; Xin-Yu Zou; Guo-Xue Song; Xu-Yong Pang; Guang-Ming Li (Mineralium Deposita, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Degradation products and transformation pathways of sulfamethoxazole chlorination disinfection by-products in constructed wetlands - Xiaoou Wang; Jiayin Li; Changping Zhang; Ming Xue; Haijiao Xie (Environmental Research, 2024)

Initial study and phylogenetic analysis of hard ticks (Acari: Ixodidae) in Nantong, China along the route of avian migration - Jian-Ming Yuan; Jing Su; Zhi-Hai Zhang; Bin Sun; Xue-Li Jiao; Xin Zhang; Yun-Peng Zhai; Yu-Jie Chen (Experimental and Applied Acarology, 2024)

Local Torrential Rainfall Event within a Mei-Yu Season Mesoscale Convective System: Importance of Back-Building Processes - Honglei Zhang; Ming Xue; Hangfeng Shen; Xiaofan Li; Guoqing Zhai (Advances in Atmospheric Sciences, 2024)

Simulation of vertical migration behaviors of heavy metals in polluted soils from arid regions in northern China under extreme weather - Zixin Xu; Ming Yin; Xue Yang; Yong Yang; Xuehui Xu; Haigang Li; Mei Hong; Guohong Qiu; Xionghan Feng; Wenfeng Tan; Hui Yin (Science of The Total Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Arbuscular mycorrhizal fungi inoculation and exogenous indole-3-acetic acid application induce antioxidant defense response to alleviate cadmium toxicity in Broussonetia papyrifera - Xue LI; Jingwei LIANG; Hongjian WEI; Yuxuan KUANG; Hui CHEN; Ming TANG; Wentao HU (Pedosphere, 2024)

Superior performance of hybrid model in ungauged basins for real-time hourly water level forecasting – A case study on the Lancang-Mekong mainstream - Zhiqiang Dong; Hongchang Hu; Hui Liu; Baoligao Baiyin; Xiangpeng Mu; Jie Wen; Dengfeng Liu; Lajiao Chen; Guanghui Ming; Xue Chen; Xiaochen Li (Journal of Hydrology, 2024)

Mapping multi-omics characteristics related to short-term PM2.5 trajectory and their impact on type 2 diabetes in middle-aged and elderly adults in Southern China - Jia-ting Wang; Wei Hu; Zhangzhi Xue; Xue Cai; Shi-yu Zhang; Fan-qin Li; Li-shan Lin; Hanzu Chen; Zelei Miao; Yue Xi; Tiannan Guo; Ju-Sheng Zheng; et al. (Journal of Hazardous Materials, 2024)

pH-shifted quinoa protein isolate-based nanocarriers for naringenin: Structure characterization and stability evaluation - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Transformation pathways of enrofloxacin chlorination disinfection by-products in constructed wetlands - Xiaoou Wang; Ming Xue; Meiyan Wang; Changping Zhang; Jiayin Li; Haijiao Xie (Chemosphere, 2024)

Postharvest application of methyl jasmonate alleviates lignin accumulation in stone cells of pear fruit during low-temperature storage - Panting Hong; Jingyi Zhang; Dongfang Shi; Can Yang; Ming Zeng; Xue Li; Kun Zhou; Wanpeng Xi (Postharvest Biology and Technology, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Always positive covalent organic nanosheet enabling pH-independent adsorption and removal of Cr(Ⅵ) - Dong-Xiao Cao; Yun-Jie Zhou; Hong-Xin Jiang; Xue-Nan Feng; Xiao-Yang Liu; Wei Li; Jing-Qi Liu; An-Na Tang; De-Ming Kong (Journal of Hazardous Materials, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Sulfadiazine chlorination disinfection by-products in constructed wetlands: Identification of biodegradation products and inference of transformation pathways - Xiaoou Wang; Jiayin Li; Meiyan Wang; Changping Zhang; Ming Xue; Haijiao Xie (Environmental Pollution, 2024)

Fracture prediction method for narrow-azimuth seismic data of offshore streamer acquisition - Dao-Li Liu; Xue-Qi Yang; Ya-Ming Zou; Xu-Min Liu; Guo-Quan Wang; Shuang-Quan Chen (Applied Geophysics, 2024)

Effects of dietary sodium acetate on growth, intestinal microbiota composition, and ammonia tolerance of juvenile yellow catfish Pelteobagrus fulvidraco - Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Aquaculture, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Sodium butyrate improves the growth performance, intestinal immunity, and ammonia tolerance of yellow catfish Pelteobagrus fulvidraco by increasing the relative abundance of Candidatus_Arthromitus - Xue Li; Shidong Wang; Muzi Zhang; Ming Li (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Thermal decomposition of magnesium carbonate in methane atmosphere for the synthesis of syngas: The effect of O2 - Qian Yin; Huiting Song; Yao Xue; Zixian Li; Huijie Liu; Yang Li; Jingyi Guo; Ming Xu; Hong Yan; Yufei Zhao; Xue Duan (Journal of Environmental Chemical Engineering, 2024)

A transition from porphyry Mo to vein-style Zn-Pb mineralization: Insights from hydrothermal fluid evolution of the Chalukou deposit, NE China - Lu-Ying Jin; Ke-Zhang Qin; Brian Rusk; Jun-Xing Zhao; Zhen-Zhen Li; Guang-Ming Li; Guo-Xue Song (Journal of Asian Earth Sciences, 2024)

High-temperature interaction mechanisms of typical igniting pyrotechnics with cellulose as the packing material - Xiao-Tao Tian; Yu-Xue Li; Ming-Hui Yu; Bing Xiao; Pei-Jin Liu; Qi-Long Yan (Fuel, 2024)

The SLC38A9–mTOR axis is involved in autophagy in the juvenile yellow catfish (Pelteobagrus fulvidraco) under ammonia stress - Xue Li; Shidong Wang; Muzi Zhang; Ming Li (Environmental Pollution, 2024)

Di-(2-ethylhexyl) phthalate exacerbates abnormalities of testicular development in F1 males via inhibition the Wnt/β-catenin signaling pathway - Nan Li; De-Ming Sun; Yong-Zhang Chang; Xue-Nan Li; Jin-Long Li; Tian-Qi Wang (Environmental Pollution, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Myricetin-based fluorescence probes with AIE and ESIPT properties for detection of hydrazine in the environment and fingerprinting - Wei Xiao; Qing Zhang; Dong Hui You; Wei Xue; Feng Peng; Nian Bing Li; Guang Ming Zhou; Hong Qun Luo (Analytica Chimica Acta, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Two new anthraquinone derivatives from Saprosma crassipes H. S. Lo - Xin-Shu Ji; De-Cai Dai; Yi-Tong Wang; Jing-Yi Cui; Hai-Xiang Li; Xin-Ming Song; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Distribution and migration of heavy metals in the sediment-plant system: Case study of a large-scale constructed wetland for sewage treatment - Rongwei Xiong; Yong Li; Xiufang Gao; Yan Xue; Jinquan Huang; Na Li; Cheng Chen; Ming Chen (Journal of Environmental Management, 2024)

Multi-omic approaches provide insights into the molecular mechanisms of Sojae semen germinatum water extract against overactive bladder - Mingchang Cheng; Yining Qiang; Yushan Wu; Xinyi Tong; Yan Tie; Zhihui Sun; Shenghan Guan; Liping Xu; Pingxiang Xu; Xiaorong Li; Ming Xue; Xuelin Zhou (Food Research International, 2024)

Application of urea-based magnetic covalent organic framework as sorbent for the determination of coumarin and its derivatives in food samples combined with liquid chromatography-mass spectrometry - Xue-Mei Nie; Yin-Long Li; Xiu-Li Xu; Feng-Ming Chen; Feng Zhang; Da Chen (Food Chemistry, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Identification and fine-mapping of QYrAS286-2BL conferring adult-plant resistance to stripe rust in cultivated emmer wheat - Yuqin Li; Yanling Hu; Yun Jiang; Qiang Zhou; Yu He; Jingshu He; Xuejiao Chen; Xue Chen; Bo Jiang; Ming Hao; Shunzong Ning; Zhongwei Yuan; et al. (Theoretical and Applied Genetics, 2024)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

A comprehensive review of seismic inversion based on neural networks - Ming Li; Xue-song Yan; Ming-zhao Zhang (Earth Science Informatics, 2023)

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Natural product osthole can significantly disrupt cell wall integrity and dynamic balance of Fusarium oxysporum - Ke Hu; Rongyu Li; Feixu Mo; Yi Ding; Aiai Zhou; Xue Guo; Ruotong Li; Min Li; Minggui Ou; Ming Li (Pesticide Biochemistry and Physiology, 2023)

Conus-wide model calibration and validation for CRESTv3.0 – An improved Coupled Routing and Excess STorage distributed hydrological model - Mengye Chen; Zhi Li; Humberto J. Vergara; Jonathan J. Gourley; Ming Xue; Yang Hong; Xiao-Ming Hu; Hector Mayol Novoa; Elinor R. Martin; Renee A. McPherson; Shang Gao; Andres Vitaliano Perez; et al. (Journal of Hydrology, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

A “Turn-on” Fluorescent Probe Based on Phenothiazine for Selectively Recognizing ClO− and its Practical Applications - Qianling Liu; Xue Li; Ming Xiao; Yin Ai; Gang Liu; Haichang Ding; Shouzhi Pu (Journal of Fluorescence, 2023)

Risk assessment of mountain tourism on the Western Sichuan Plateau, China - Yu-Qing Zhang; Yue-Lin Wang; Hong Li; Xue-Ming Li (Journal of Mountain Science, 2023)

Ent-eudesmane sesquiterpenoids from the Chinese liverwort Chiloscyphus polyanthus - Ming-Zhu Zhu; Yi Li; Jin-Chuan Zhou; Dong-Xue Lv; Xiao-Jie Fu; Zhen Liang; Shuang-Zhi Yuan; Jing-Jing Han; Jiao-Zhen Zhang; Ze-Jun Xu; Wen-Qiang Chang; Hong-Xiang Lou (Phytochemistry, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Fully waste-based solar evaporator in interfacial solar-driven seawater desalination - Yuming Wu; Xin Zhong; Youquan Li; Huan Li; Yongshuang Cai; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Journal of Environmental Chemical Engineering, 2023)

Effects of ammonia and roxithromycin exposure on skin mucus microbiota composition and immune response of juvenile yellow catfish Pelteobagrus fulvidraco - Donghao Yuan; Shidong Wang; Xue Li; Muzi Zhang; Ming Li (Fish & Shellfish Immunology, 2023)

Fe3O4-polyvinyl alcohol sponge as photo-absorber in interfacial solar steam generation - Zhihui Yang; Yuming Wu; Chenxi Han; Yipeng Quan; Youquan Li; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Desalination, 2023)

One-step conversion of corn stalk to glucose and furfural in molten salt hydrate/organic solvent biphasic system - Yu Li; Li-Li Sun; De-Ming Cao; Xue-Fei Cao; Shao-Ni Sun (Bioresource Technology, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Turnover polypyrrole decorated cotton fabric based solar evaporator for cost-effective and steady desalination - Xin Zhong; Yuming Wu; Pu Zhang; Yibing Chen; Yongshuang Cai; Weiming Wang; Xue Min; Jun Xiong; Ming Li (Journal of Cleaner Production, 2023)

Pathways to increase maize yield in Northwest China: A multi-year, multi-variety analysis - Yugang Wang; Guoqiang Zhang; Rongfa Li; Keru Wang; Bo Ming; Peng Hou; Ruizhi Xie; Jun Xue; Shaokun Li (European Journal of Agronomy, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Effect and Mechanism of Sodium Butyrate on Neuronal Recovery and Prognosis in Diabetic Stroke - Ting-ting Li; Deng-ming Zhao; Yu-ting Wei; Jing-bo Li; Xue-fei Li; Qiang Wan; Xin Zhang; Xiang-nan Liu; Wan-chao Yang; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Laboratory investigation on fumes generated by different modified asphalt binders - Hui Li; Ming Jia; Xue Zhang; Zipeng Wang; Yiding Liu; Jie Yang; Bing Yang; Yang Sun; Hanbing Wang; Hongwei Ma (Transportation Research Part D: Transport and Environment, 2023)

Phytoecdysteroids from Dianthus superbus L.: Structures and anti-neuroinflammatory evaluation - Xue-Li Hou; Yu-Qi Gao; Jing-Hui Yang; Han-Wu Liu; Meng-Meng Bai; Zhen-Hai Wu; Chun-Huan Li; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Fabrication of modified electrode by reduced graphene oxide (rGO) and polyaniline (PANI) for enhancing azo dye decolorization in bio-electrochemical systems (BESs) - Ai-Hong Chen; Yue-Jia Yang; Shuai Wang; Li-Ming Yang; Xue-Yun Gao; Dan Cui (Environmental Research, 2023)

Solar-driven dry reforming of methane using RuNi single-atom alloy catalyst coupled with thermal decomposition of carbonates - Qian Yin; Tianyang Shen; Jinhao Li; Chenjun Ning; Yao Xue; Guangbo Chen; Ming Xu; Fenglong Wang; Yu-Fei Song; Yufei Zhao; Xue Duan (Chemical Engineering Journal, 2023)

S, Fe dual doped and precisely regulated CoP porous nanoneedle arrays for efficient hydrogen evolution at 3 A cm−2 - Meng-Xuan Li; Yu Ma; Bo Xiao; Ya-Nan Zhou; Wen-Li Yu; Xue-Jun Zhai; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

In-situ Fluid Phase Variation along the Thermal Maturation Gradient in Shale Petroleum Systems and Its Impact on Well Production Performance - Qianyou Wang; Wei Yang; Yaohua Li; Zhenxue Jiang; Ming Wen; Rusi Zuo; Xin Wang; Zixin Xue; Yaohua Wang (Journal of Earth Science, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Comparative analysis of the gut microbiota of wild wintering whooper swans (Cygnus Cygnus), captive black swans (Cygnus Atratus), and mute swans (Cygnus Olor) in Sanmenxia Swan National Wetland Park of China - Jun-Xian Mi; Kai-Li Liu; Wen-Li Ding; Ming-Hui Zhang; Xue-Fei Wang; Aftab Shaukat; Mujeeb Ur Rehman; Xi-Lan Jiao; Shu-Cheng Huang (Environmental Science and Pollution Research, 2023)

Hydroxyl radical dominated ibuprofen degradation by UV/percarbonate process: Response surface methodology optimization, toxicity, and cost evaluation - Honghai Xue; Jinying Li; Genbao Zhang; Ming Li; Binshuo Liu; Chunli Kang (Chemosphere, 2023)

Reducing plastic film mulching and optimizing agronomic management can ensure food security and reduce carbon emissions in irrigated maize areas - Guoqiang Zhang; Bo Ming; Ruizhi Xie; Jianglu Chen; Peng Hou; Jun Xue; Dongping Shen; Rongfa Li; Juan Zhai; Yuanmeng Zhang; Keru Wang; Shaokun Li (Science of The Total Environment, 2023)

Unique recognition of the microalgal plastidial glycerol-3-phosphate acyltransferase for acyl-ACP - Xianglong Li; Miao Yang; Dongru Sun; Jianping Shi; Ming Yang; Yanbin Feng; Song Xue (Plant Science, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

Inulin acetate as a novel recombinant subunit vaccine carrier for immunization of tilapia against tilapia lake virus - Yu-Ying Zheng; Yang Li; Tian-Zi Sun; Xue-Feng Wei; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Bin Zhu (Aquaculture, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Bacteroides rhinocerotis sp. nov., isolated from the fresh feces of rhinoceros in Beijing Zoo - Xue Li; Peilin Sun; Liang Gong; Weixiong Shi; Zhiguang Xiang; Ming Li; Lei Su; Chuan Qin (Archives of Microbiology, 2023)

Lactococcus intestinalis sp. nov., a new lactic acid bacterium isolated from intestinal contents in Alzheimer’s disease mice - Peilin Sun; Xue Li; Weixiong Shi; Ling Zhang; Ming Li; Lei Su; Chuan Qin (Antonie van Leeuwenhoek, 2023)

Degradation and transformation of linear alkyl-benzene sulfonates (LAS) in integrated constructed wetland–microbial fuel cell systems - Huixin Wang; Xiaoou Wang; Meiyan Wang; Changping Zhang; Jiayin Li; Ming Xue; Weiyi Xia; Haijiao Xie (Chemosphere, 2023)

Regional-modal optimization problems and corresponding normal search particle swarm optimization algorithm - Yi-li Yuan; Chang-ming Hu; Liang Li; Yuan Mei; Xue-yan Wang (Swarm and Evolutionary Computation, 2023)

Numerical investigations of the micro lunar dust particles deposition in the human oral respiratory airway - Xinguang Cui; Wei Song; Yuan Xue; Hanxiong Guan; Jinhua Zhang; Xinxing He; Honglei Ma; Ming Lei; Jintao Wang; Yichao Li (Journal of Hazardous Materials, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

An environmentally insensitive fluorescent probe for G4 DNA detection: Design, synthesis, and mechanism studies - Xue-Xian Lang; Shu-Hui Sun; Hao-Wen Cao; Yan-Song Chen; Hong-Yao Li; Ming-Qi Wang (Analytica Chimica Acta, 2023)

Tree density reduction mitigates the decline of Larix principis-rupprechtii plantations: Evidence from a combination of dendroclimatic and physiological measurements - Qian-Nan Leng; Xue-Wei Gong; Ming-Yong Li; Guang-You Hao (Agricultural and Forest Meteorology, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

Real-World Underwater Image Enhancement Based on Attention U-Net - Pengfei Tang; Liangliang Li; Yuan Xue; Ming Lv; Zhenhong Jia; Hongbing Ma (Journal of Marine Science and Engineering, 2023)
In recent years, with the increasingly serious problems of resource shortage and environmental pollution, the exploration and development of underwater clean energy were particularly important. At the same time, abundant underwater resources and species have attracted a large number of scientists to carry out research on underwater-related tasks. Due to the diversity and complexity of underwater environments, it is difficult to perform related vision tasks, such as underwater target detection and capture. The development of digital image technology has been relatively mature, and it has been applied in many fields and achieved remarkable results, but the research on underwater image processing technology is rarely effective. The underwater environment is much more complicated than that on land, and there is no light source underwater. Underwater imaging systems must rely on artificial light sources for illumination. When light travels through water, it is severely attenuated by water absorption, reflection, and scattering. The collected underwater images inevitably have problems such as limited visible range, blur, low contrast, uneven illumination, incoherent colors, and noise. The purpose of image enhancement is to improve or solve one or more of the above problems in a targeted manner. Therefore, underwater image enhancement technology has become one of the key contents of underwater image processing technology research. In this paper, we proposed a conditional generative adversarial network model based on attention U-Net which contains an attention gate mechanism that could filter invalid feature information and capture contour, local texture, and style information effectively. Furthermore, we formulate an objective function through three different loss functions, which can evaluate image quality from global content, color, and structural information. Finally, we performed end-to-end training on the UIEB real-world underwater image dataset. The comparison experiments show that our method outperforms all comparative methods, the ablation experiments show that the loss function proposed in this paper outperforms a single loss function, and finally, the generalizability of our method is verified by executing on two different datasets, UIEB and EUVP.

An experimental study on recovering and concentrating ammonia by sweep gas membrane distillation - Zhan Li; Pengfei Zhang; Kecheng Guan; Ralph Rolly Gonzales; Toru Ishigami; Ming Xue; Tomohisa Yoshioka; Hideto Matsuyama (Process Safety and Environmental Protection, 2023)

Free astaxanthin-rich diets enhanced astaxanthin accumulation in egg yolks compared to esterified astaxanthin-rich diets - Ying-Cai Zhao; Xiao-Yue Li; Cheng-Cheng Wang; Jin-Yue Yang; Chang-Hu Xue; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2023)

Concomitant oxidation of fatty acids other than DHA and EPA plays a role in the characteristic off-odor of fish oil - Yun-Qi Wen; Chang-Hu Xue; Hong-Wei Zhang; Li-Li Xu; Xiao-Han Wang; Shi-Jie Bi; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Selenium anion substitution endows manganese sulfide as a bifunctional electrocatalyst for efficient water splitting in alkaline solutions - Beibei Sun; Guohua Dong; Jun Ye; Dong-feng Chai; Xue Yang; Shanshan Fu; Ming Zhao; Wenzhi Zhang; Jinlong Li (Chemical Engineering Journal, 2023)

Characterizing formation mechanisms of secondary aerosols on black carbon in a megacity in South China - Jing Wei; Ying-Bo Niu; Meng-Xue Tang; Yan Peng; Li-Ming Cao; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2023)

Enhanced removal of typical odor compounds in constructed wetlands integrated with iron carbon and tidal flow - Yuwei She; Yan Zhao; Hongyan Ding; Qian Feng; Zhaoxia Xue; Jingyang Luo; Minfeng Lu; Qian Hu; Jiashun Cao; Yu Dai; Ming Li (Journal of Water Process Engineering, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Bifunctional honeycomb hierarchical structured 3D/3D ReS2/ZnIn2S4-Sv heterojunction for efficient photocatalytic H2-evolution integrated with biomass oxidation - Jundie Hu; Xue Li; Jiafu Qu; Xiaogang Yang; Yahui Cai; Tingyu Yang; Fengyi Yang; Chang Ming Li (Chemical Engineering Journal, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

A global analysis of dry matter accumulation and allocation for maize yield breakthrough from 1.0 to 25.0 Mg ha−1 - Guangzhou Liu; Yunshan Yang; Xiaoxia Guo; Wanmao Liu; Ruizhi Xie; Bo Ming; Jun Xue; Keru Wang; Shaokun Li; Peng Hou (Resources, Conservation and Recycling, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Freezing-induced loss of wheat starch granule-associated proteins affected dough quality: From water distribution, rheological properties, microstructure, and gluten development - Han Tao; Fan Lu; Xue-Feng Zhu; Hui-Li Wang; Xue-Ming Xu (Journal of Cereal Science, 2023)

A chemometric study on the identification of 5-methylfurfural and 2-acetylfuran as particular volatile compounds of oxidized fish oil based on SHS-GC-IMS - Yun-Qi Wen; Hong-Wei Zhang; Chang-Hu Xue; Xiao-Han Wang; Shi-Jie Bi; Li-Li Xu; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Melt-stretched poly(vinylidene fluoride)/zinc oxide nanocomposite films with enhanced piezoelectricity by stress concentrations in piezoelectric domains for wearable electronics - Ming Yuan; Ruixue Ma; Qiuyang Ye; Xue Bai; Hanchuan Li; Feifei Yan; Chuntai Liu; Yue Ren; Zhen Wang (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Comparison of infections with respiratory syncytial virus between children and adults: a multicenter surveillance from 2015 to 2019 in Beijing, China - Ming Luo; Cheng Gong; Yan Zhang; Xue Wang; Yang Liu; Qing Luo; Maozhong Li; Aihua Li; Yiting Wang; Mei Dong; Wenbo Xu; Fang Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Temporal dynamics of microcystins in two reservoirs with different trophic status during the early growth stage of cyanobacteria - Qingju Xue; Ming Kong; Liqiang Xie; Tong Li; Mengna Liao; Zebin Yan; Yanyan Zhao (Environmental Science and Pollution Research, 2022)

Receipt of inactivated COVID-19 vaccine had no adverse influence on embryo implantation, clinical pregnancy and miscarriage in early pregnancy - Yapeng Wang; Xiulian Ren; Zhongwei Wang; Xue Feng; Ming Li; Ping Liu (Science China Life Sciences, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Starvation shrinks the mussel foot secretory glands and impairs the byssal attachment - Yi Zheng; Yue-Ming Yang; Yue-Feng Xu; Yu-Qing Wang; Xue Shi; Gao-Hai Zheng; Yi-Feng Li (Frontiers in Marine Science, 2022)
Mussel is an economically and ecologically important species widely distributed throughout the world. The mussel adheres to the attachment substrate by secreting byssus external to the body. Various environmental and biological factors influence the process of byssus secretion, and the present study investigated the effect of starvation on byssal secretion in the hard-shelled mussel Mytilus coruscus . Histological changes in mussel foot secretory glands and gene expression of mussel foot proteins were also determined. The experimental setup consisted of starvation treatments for 7, 14 and 21 days, and the control groups. The results showed that the number of produced byssus was higher in the starvation group compared to the control (CTR) group, and the starvation group had a significantly higher of byssal shedding number from 6 days of starvation treatment onwards ( p < 0.05). The byssal thread diameter was significantly reduced in all starvation treatment groups ( p < 0.05). However, starvation treatment had no effect on the length of the byssal thread ( p > 0.05). After 21 days of starvation treatment, the byssal thread volume was significantly lower than that of the CTR group ( p < 0.05). A significant decrease in the breaking force of the byssal thread was observed after 14 and 21 days of starvation treatment ( p < 0.05), along with an upward shift in the breakpoints. Starvation treatment significantly reduced the percentage of foot secretory glands area to total tissue ( p < 0.05). The expression of the mussel foot protein genes ( Mcfp-1P and Mcfp-1T ) was significantly up-regulated at 7 days of starvation treatment ( p < 0.05). These findings reveal that starvation weakens byssal thread performance by influencing mussel foot secretory glands, which increases the dislodgment risks of suspended-cultured mussels.

Effects of saline-alkali stress on bacterial and fungal community diversity in Leymus chinensis rhizosphere soil - Binshuo Liu; Yunhang Hu; Ying Wang; Honghai Xue; Zhonghe Li; Ming Li (Environmental Science and Pollution Research, 2022)

Knockdown of lncRNA MIAT attenuated lipopolysaccharide-induced microglial cells injury by sponging miR-613 - Jia Li; Chang-Lin Zou; Zhi-Ming Zhang; Feng Xue (Mammalian Genome, 2022)

Potential antibacterial and anti-biofilm effects of Anoectochilus roxburghii rhizome cultures - Ming-Zhi Fan; Xiao-Long Jiang; Xuan-Chun Piao; Xue-Feng Li; Mei-Yu Jin; Mei-Lan Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Two new bioactive secondary metabolites from the endophytic fungus Talaromyces assiutensis JTY2 - Ying-Li Li; Ji-Ling Yi; Jin Cai; Xue-Ming Zhou; Li Chen; Xin Zhuo; Xin-Yi Lai (Natural Product Research, 2022)

Knockdown of Two Iodothyronine Deiodinase Genes Inhibits Epinephrine-Induced Larval Metamorphosis of the Hard-Shelled Mussel Mytilus coruscus - Xue Shi; Yu-Qing Wang; Yue-Ming Yang; Yi-Feng Li (Frontiers in Marine Science, 2022)
The metamorphosis process is a critical life-changing event for marine invertebrate planktonic larvae to transform into benthic adults, which is crucial for the shellfish bed’s ecosystem stability and seed production in aquaculture. The mechanism of neuroendocrine regulation in the larval metamorphosis of bivalves remains ambiguous. In the present study, the expression of two deiodinase genes, McDx and McDy , was analyzed by whole-mount in situ hybridization at four larval stages in the hard-shelled mussel Mytilus coruscus . The McDx and McDy localized in visceral tissues, nervous system, mantle, and velum, indicating that two deiodinase genes are essential for larval development in M. coruscus . Knockdown of the McDx and McDy in the pediveliger larvae of M. coruscus using electroporation of siRNA significantly ( p < 0.001) reduced McDx and McDy expression. McDx and McDy knockdown reduced larval metamorphosis in 45% and 49% of the pediveliger larvae induced by epinephrine (EPI). It is hypothesised that the knockdown effects of McDx and McDy repress metamorphic induction rather than larval viability, which does not elicit a lethal effect. The present study corroborates a synergistic action of the adrenergic and thyroid hormones signalling pathway in M. coruscus , and suggests the role of McDx and McDy in larval development and metamorphic transition.

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Carbon emission efficiency and spatio-temporal dynamic evolution of the cities in Beijing-Tianjin-Hebei Region, China - Li-Ming Xue; Zhi-Xue Zheng; Shuo Meng; Mingjun Li; Huaqing Li; Ji-Ming Chen (Environment, Development and Sustainability, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Transcriptome revealing the dual regulatory mechanism of ethylene on the rhynchophylline and isorhynchophylline in Uncaria rhynchophylla - Xue Li; Xiao-hong Wang; Wei Qiang; Hao-jie Zheng; Li-yang ShangGuan; Ming-sheng Zhang (Journal of Plant Research, 2022)

Metagenomic insights into the environmental adaptation and metabolism of Candidatus Haloplasmatales, one archaeal order thriving in saline lakes - Heng Zhou; Dahe Zhao; Shengjie Zhang; Qiong Xue; Manqi Zhang; Haiying Yu; Jian Zhou; Ming Li; Sumit Kumar; Hua Xiang (Environmental Microbiology, 2022)
Summary The KTK 4A‐related Thermoplasmata thrives in the sediment of saline lakes; however, systematic research on its taxonomy, environmental adaptation and metabolism is lacking. Here, we detected this abundant lineage in the sediment of five artificially separated ponds (salinity 7.0%–33.0%) within a Chinese soda‐saline lake using culture‐independent metagenomics and archaeal 16S rRNA gene amplicons. The phylogenies based on the 16S rRNA gene, and 122 archaeal ubiquitous single‐copy proteins and genome‐level identity analyses among the metagenome‐assembled genomes demonstrate this lineage forming a novel order, Candidatus Haloplasmatales, comprising four genera affiliated with the identical family. Isoelectric point profiles of predicted proteomes suggest that most members adopt the energetically favourable ‘salt‐in’ strategy. Functional prediction indicates the lithoheterotrophic nature with the versatile metabolic potentials for carbohydrate and organic acids as well as carbon monoxide and hydrogen utilization. Additionally, hydrogenase genes hdrABC ‐ mvhADG are linked with incomplete reductive citrate cycle genes in the genomes, suggesting their functional connection. Comparison with the coupling of HdrABC‐MvhADG and methanogenesis pathway provides new insights into the compatibility of laterally acquired methanogenesis with energy metabolism in the related order Methanomassiliicoccales . Globally, our research sheds light on the taxonomy, environmental adaptative mechanisms, metabolic potentials and evolutional significance of Ca . Haloplasmatales.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Effects of Environmental Cadmium on Cadmium Accumulation, Oxidative Response, and Microelements Regulation in the Liver and Kidney of Hexagrammos otakii - Fawen Hu; Ming Sun; Li Li; Fengxiang Gao; Yuxia Jian; Xue Wang; Xiaolong Wang; Wen Guo (Journal of Ocean University of China, 2022)

Characteristics of circRNAs expression profiles in the piglets intestine induced by oxidative stress - Zhi-xin Li; Wei Chen; Ming Qin; Li-xue Wang; Yong-qing Zeng (Genes & Genomics, 2022)

Cultivation of arbuscular mycorrhizal Broussonetia papyrifera seedlings by planting the mycorrhizal nurse plant downwards - Zhihao Wang; Jingwei Liang; Yuxuan Kuang; Xue Li; Hui Chen; Ming Tang; Wentao Hu (Mycorrhiza, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Comparative transcriptome analysis revealed the molecular mechanism of the effect of light intensity on the accumulation of rhynchophylline and isorhynchophylline in Uncaria rhynchophylla - Xiao-Hong Wang; Xue Li; Wei Qiang; Xiao-Song Yu; Hao-Jie Zheng; Ming-Sheng Zhang (Physiology and Molecular Biology of Plants, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Analysis on shadow price and abatement potential of carbon dioxide in China’s provincial industrial sectors - Zhaoquan Xue; Hailin Mu; Nan Li; Ming Zhang (Environmental Science and Pollution Research, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Long non-coding RNA TTC28-AS1 attenuates high glucose-induced damage in HK-2 cells depending on the regulation of miR-320a/CD2AP axis - Ji Zhang; Juan Ding; Ming Yu; Fang Li; Xue Zhou; Hongxia Shuai (Genes & Genomics, 2021)

Optimization of immunization procedure for SWCNTs‐based subunit vaccine with mannose modification against spring viraemia of carp virus in common carp - Yu‐Ming Gong; Chen Zhang; Yang Li; Guo Chen; Gao‐Xue Wang; Bin Zhu (Journal of Fish Diseases, 2021)
Immersion vaccination of single‐walled carbon nanotubes loaded with mannose‐modified glycoprotein (SWCNTs‐MG) vaccine has been proved to be effective in preventing spring viraemia of carp virus (SVCV). Immunization procedure has immense consequence on the immune effect of the immersion vaccine. However, immunization procedure optimization for SWCNTs‐MG vaccine against SVCV has not been reported. In this study, accordingly, a full‐factor experiment was designed to optimize the immunization procedure of SWCNTs‐MG vaccine by three aspects of vaccine dose (30 mg/L, 40 mg/L and 50 mg/L), immunization density (8 fish L −1 , 24 fish L −1 and 48 fish L −1 ) and immunization time (6, 12 and 24 hr). Furthermore, we used the immunization group (A1B2C1, 30 mg/L, 24 fish L −1 and 6 hr) in the previous study as a positive control (PC) to evaluate the immunization effect optimized conditions from the expression of immune‐related genes and relative percentage survival (RPS). At 28 days post‐vaccination (DPV), common carps were intraperitoneal injected SVCV challenged test indicated that the A1B2C2 group (30 mg/L, 24 fish L −1 , 12 hr) displayed superiority of protective efficacy compare with other groups and the RPS with 77.9%, which was 15.6% higher than the PC group of RPS with 62.3%. Moreover, the expression of immune‐related genes such as IL‐10 , CD4 and MHC‐II was also significantly higher than PC group. The specific experimental flow chart is shown in Figure 1 . Conclusively, these results demonstrated that vaccine dose, immunization density and immunization time are 30 mg/L, 24 fish L −1 and 12 hr, which is the more appropriate immunization programme with juvenile carp for SWCNTs‐MG vaccine. This study provides a profitable reference for improving the immune efficiency of aquatic immersion vaccine. The experiment process and timeline chart of the present research image

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Highly integrated adaptive mechanisms in Spiribacter halalkaliphilus , a bacterium abundant in Chinese soda‐saline lakes - Qiong Xue; Dahe Zhao; Shengjie Zhang; Heng Zhou; Zhenqiang Zuo; Jian Zhou; Ming Li; Hua Xiang (Environmental Microbiology, 2021)
Summary Soda‐saline lakes are polyextreme environments inhabited by many haloalkaliphiles, including one of the most abundant Spiribacter species. However, its mechanisms of adaptation are not ecophysiologically characterized. Based on a large‐scale cultivation strategy, we obtained a representative isolate of this Spiribacter species whose relative abundance was the highest (up to 15.63%) in a wide range of salinities in the soda‐saline lakes in Inner Mongolia, China. This species is a chemoorganoheterotrophic haloalkaliphile. It has a small and streamlined genome and utilizes a wide variety of compatible solutes to resist osmotic pressure and multiple monovalent cation/proton antiporters for pH homeostasis. In addition to growth enhancement by light under microaerobic conditions, cell growth, organic substrate consumption and polyhydroxybutyrate biosynthesis were also improved by inorganic sulfide. Both quantitative RT‐PCR and enzymatic assays verified that sulfide:quinone oxidoreductase was upregulated during this process. Metatranscriptomic analysis indicated that all genes related to environmental adaptation were transcribed in natural environments. Overall, this study has identified a novel abundant haloalkaliphile with multiple and highly integrated adaptive strategies and found that inorganic sulfide was able to improve the adaptation of a heterotroph to polyextreme environments.

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Cross‐phytogroup assessment of foliar epiphytic mycobiomes - Ting Zhu; Jia Yao; Hao Liu; Chen‐Hao Zhou; Yuan‐Zhan Liu; Zheng‐Wei Wang; Zhe‐Xue Quan; Bo Li; Ji Yang; Wei‐Chang Huang; Ming Nie (Environmental Microbiology, 2021)
Summary The foliar surface forms one of the largest aboveground habitats on Earth and maintains plant‐fungus relationships that greatly affect ecosystem functioning. Despite many studies with particular plant species, the foliar epiphytic mycobiome has not been studied across a large number of plant species from different taxa. Using high‐throughput sequencing, we assessed epiphytic mycobiomes on leaf surfaces of 592 plant species in a botanical garden. Plants of angiosperms, gymnosperms, and pteridophytes were involved. Plant taxonomy, leaf side, growing environment, and evolutionary relationships were considered. We found that pteridophytes showed the higher fungal species diversity, stronger mutualistic fungal interactions, and a greater percentage of putative pathogens than gymnosperms and angiosperms. Plant taxonomic group, leaf side, and growing environment were significantly associated with the foliar epiphytic mycobiome, but the similarity of the mycobiomes among plants was not directly related to the distance of the host evolutionary tree. Our results provide a general understanding of the foliar fungal mycobiomes from pteridophytes to angiosperms. These findings will facilitate our understanding of foliar fungal epiphytes and their roles in plant communities and ecosystems.

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

rno-miR-128-3p promotes apoptosis in rat granulosa cells (GCs) induced by norepinephrine through Wilms tumor 1 (WT1) - Ming Li; Ling Xue; Weibin Xu; Pingping Liu; Feng Li (In Vitro Cellular & Developmental Biology - Animal, 2021)
The mechanism related to ovarian follicular is complex, which has not been fully elucidated. Abundant reports have confirmed that the ovarian function development is closely related to sympathetic innervation. As one of the major neurotransmitters, norepinephrine (NE) is considered an effective regulator of ovarian functions like granulosa cell (GC) apoptosis. However, the mechanism between NE and GC apoptosis in rat is still unclear. In our study, GCs were isolated and cultured in vitro with NE treatment. The apoptosis of GCs was facilitated by NE. Wilms tumor 1 (WT1) was found to be significantly downregulated in GCs after NE treatment, and overexpression of WT1 repressed apoptosis in rat GCs induced by NE. rno-miR-128-3p was found to be significantly enhanced by NE in GCs, and inhibition of rno-miR-128-3p repressed apoptosis in rat GCs induced by NE. Mechanistically, rno-miR-128-3p interacted with WT1 and repressed its expression. In summary, inhibition of rno-miR-128-3p may enhance WT1 expression, and then repress NE-induced apoptosis in rat GCs. Our research may provide a new insight for the improvement of ovarian follicular development.

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Involvement of Putrescine, Nitric Oxide, and Hydrogen Peroxide in Methyl Jasmonate-Induced Ginsenoside Synthesis in Adventitious Root Cultures of Panax ginseng C.A. Meyer - Xiao-Han Wu; Ming-Zhi Fan; Xue-Feng Li; Xuan-Chun Piao; Ri Gao; Mei-Lan Lian (Journal of Plant Growth Regulation, 2021)

Convergence analysis of regional marginal abatement cost of carbon dioxide in China based on spatial panel data models - Zhaoquan Xue; Nan Li; Hailin Mu; Ming Zhang; Jingru Pang (Environmental Science and Pollution Research, 2021)

OSL chronology of a Palaeolithic site in a humid subtropical mountainous area of southeast China - Jian-hui Jin; Xiao-yang Wang; Zhen-yu Zhou; Yun-ming Huang; Xue-chun Fan; Xin-xin Zuo; Zhi-zhong Li; Zhi-yong Ling; Yong-qing Ren; Shu-tong Li (Journal of Mountain Science, 2021)

Affinibrenneria salicis gen. nov. sp. nov. isolated from Salix matsudana bark canker - Dan-ran Bian; Han Xue; Guang-ming Wang; Chun-gen Piao; Yong Li (Archives of Microbiology, 2021)

Characterization of Organic Aerosol at a Rural Site in the North China Plain Region: Sources, Volatility and Organonitrates - Qiao Zhu; Li-Ming Cao; Meng-Xue Tang; Xiao-Feng Huang; Eri Saikawa; Ling-Yan He (Advances in Atmospheric Sciences, 2021)

Isolation and characterization of a new cytotoxic polyketide–amino acid hybrid from Thermothelomyces thermophilus ATCC 42464 - Yang-Le Gao; Ming-Liang Zhang; Xue Wang; Huai-Dong Zhang; Jian-Zhong Huang; Li Li (Natural Product Research, 2021)

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

Carbon and nitrogen budget in fish-polychaete integrated aquaculture system - Fawen Hu; Ming Sun; Jinghui Fang; Guodong Wang; Li Li; Fengxiang Gao; Yuxia Jian; Xue Wang; Guangbin Liu; Yan Zou; Wen Guo (Journal of Oceanology and Limnology, 2021)

Vegetation dynamics and climate variability over the past 2000 years inferred from Son Kul marsh in the western Tianshan Mountains - Dong-liang Zhang; Yao-ming Li; Kai-hui Li; Xue-xi Ma; Yun-peng Yang (Journal of Mountain Science, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Biotransformation of Phlorizin by Eurotium cristatum to Increase the Antioxidant and Antibacterial Activity of Docynia indica Leaves - Jie Xie; Jiang Chen; Xue-ran Mei; Ming-jun Zhu; Xue-li Li; Juan Du; Xiao-yu Zhang (Current Microbiology, 2021)

The changes of brain functional networks in young adult smokers based on independent component analysis - XianFu Wang; Ting Xue; Fang Dong; Yangding Li; Dongdong Xie; Chang Liu; Ming Zhang; Yanzhi Bi; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

Photochemical degradation kinetics and mechanisms of norfloxacin and oxytetracycline - Honghai Xue; Ming Li; Binshuo Liu; Qingling Meng (Environmental Science and Pollution Research, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Synthesis and molecular docking studies of novel pyrimidine derivatives as potential antibacterial agents - Xue-Qian Bai; Chun-Shi Li; Ming-Yue Cui; Ze-Wen Song; Xing-Yu Zhou; Chao Zhang; Yang Zhao; Tian-Yi Zhang; Tie-Yan Jiang (Molecular Diversity, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

A new triterpenoid glucoside from Leucas zeylanica - Guang-Ying Chen; Bin Zhang; Ting Zhao; Najat Nidhal; Wang Jia-Li; Xue-Ming Zhou; Dai Chun-Yan (Natural Product Research, 2020)

Deep RNA-seq analysis reveals key responding aspects of wild banana relative resistance to Fusarium oxysporum f. sp. cubense tropical race 4 - Wei-Ming Li; Miguel Dita; Mathieu Rouard; Wei Wu; Nicolas Roux; Jiang-Hui Xie; Xue-Jun Ge (Functional & Integrative Genomics, 2020)

Comparison of third-generation sequencing approaches to identify viral pathogens under public health emergency conditions - Yang Li; Xiao-zhou He; Ming-hui Li; Bo Li; Meng-jie Yang; Yao Xie; Yi Zhang; Xue-jun Ma (Virus Genes, 2020)

Impacts of Climate and Nutrients on Carbon Sequestration Rate by Wetlands: A Meta-analysis - Caifeng Cheng; Min Li; Zhenshan Xue; Zongsheng Zhang; Xianguo Lyu; Ming Jiang; Hongri Zhang (Chinese Geographical Science, 2020)

Molecular cloning and expression analysis of myd88 from oriental weatherfish ( Misgurnus anguillicaudatus ) in response to bacterial challenge - Jian H. Chen; Xue Li; Meng J. Wang; Chun M. Wang; Yan Q. Peng; Hai H. Wang; Ming Zhu (Journal of Fish Biology, 2020)
Myeloid differentiation factor 88 (Myd88) plays an important role in both innate and adaptive immune response. In this study, the full‐length complementary DNA (cDNA) of myd88 from Misgurnus anguillicaudatus was characterized. The myd88 cDNA is 1333 bp in length and contains an 855 bp open reading frame encoding a predicted protein of 284 amino acids. The predicted protein possesses typical Myd88 domain structural features including a death domain in the N‐terminus, and box 1, 2, and 3 motifs of the Toll/IL‐1 receptor domain in the C‐terminus. Quantitative real‐time PCR (qRT‐PCR) revealed that myd88 messenger RNA (mRNA) was ubiquitously expressed in all examined tissues, especially highly in brain, kidney, blood, intestines and liver. qRT‐PCR and western blotting were used to determine the mRNA and protein levels of Myd88 after Aeromonas veronii challenge, respectively. The Myd88 was remarkably upregulated in response to infection of A. veronii. These results suggested that Myd88 may play a vital role during the immune response of M. anguillicaudatus against bacterial infection.

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

The interaction between dietary marine components and intestinal flora - Lin Li; Chang-Hu Xue; Tian-Tian Zhang; Yu-Ming Wang (Marine Life Science & Technology, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Synergetic effect between adsorption and photodegradation on rGO/TiO2/ACF composites for dynamic toluene gaseous removal - Yuwei Li; Fang Liu; Meng Li; Xuye Wang; Xuejin Qi; Wei Li; Ming Xue; Yongqiang Wang; Fenglei Han (Environmental Science and Pollution Research, 2020)

Anti-inflammatory bibenzyls from the stems of Dendrobium huoshanense via bioassay guided isolation - Qiang-Ming Li; Hui Jiang; Xue-Qiang Zha; De-Ling Wu; Li-Hua Pan; Jun Duan; Jian Liu; Jian-Ping Luo (Natural Product Research, 2020)

Synthesis and application of Cu-BTC@ZSM-5 composites as effective adsorbents for removal of toluene gas under moist ambience: kinetics, thermodynamics, and mechanism studies - Meng Li; Yuwei Li; Wei Li; Fang Liu; Xuejin Qi; Ming Xue; Yongqiang Wang; Chaocheng Zhao (Environmental Science and Pollution Research, 2020)

Comprehensive strength deterioration model of compacted loess exposed to drying-wetting cycles - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2020)

MiR-26a promotes fracture healing of nonunion rats possibly by targeting SOSTDC1 and further activating Wnt/β-catenin signaling pathway - Liang Sun; Zhong Li; Hanzhong Xue; Teng Ma; Cheng Ren; Ming Li; Yao Lu; He Sun; Kun Zhang (Molecular and Cellular Biochemistry, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Modification of the gravity increase method in slope stability analysis - Chang-ming Hu; Yi-li Yuan; Yuan Mei; Xue-yan Wang; Zheng Liu (Bulletin of Engineering Geology and the Environment, 2019)

Protective effect of isoliquiritigenin against cerebral injury in septic mice via attenuation of NF-κB - Peng Zou; Hong-Ming Ji; Jian-Wei Zhao; Xin-Min Ding; Zi-Gang Zhen; Xuan Zhang; Xiao-Qi Nie; Li-Xiong Xue (Inflammopharmacology, 2019)

Molecular Fingerprints of Soil Organic Matter in a Typical Freshwater Wetland in Northeast China - Zhe Li; Zhongsheng Zhang; Zhenshan Xue; Xiaolin Song; Hongri Zhang; Haitao Wu; Ming Jiang; Xianguo Lyu (Chinese Geographical Science, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Benthic foraminiferal fauna and sediment provenance of Eocene syn-rift sequences in Taiwan: implication for onset of Asian epi-continental marginal seas off China coast - Chi-Yue Huang; Lei Shao; Ming-Huei Wang; Wei-Guang Xue; Pei-Jun Qiao; Yu-Chi Cui; Yuan-Li Hou (Marine Geophysical Research, 2019)

Identification of duplicated Cited3 genes and their responses to hypoxic stress in blunt snout bream (Megalobrama amblycephala) - Hong-Hong Guo; Yuan Sun; Xue-li Zhang; Xia-Yun Jiang; Shu-Ming Zou (Fish Physiology and Biochemistry, 2019)

Benzopyran derivatives from endophytic Daldinia eschscholzii JC-15 in Dendrobium chrysotoxum and their bioactivities - Ming Hu; Xue-Qiong Yang; Qing-Yan Zhou; Shu-Quan Li; Bang-Yan Wang; Bao-Hui Ruan; Ya-Bin Yang; Zhuo-Xi Zhang; Hao Zhou; Zhong-Tao Ding (Natural Product Research, 2019)

A reliable non-invasive PCR method for takin (Budorcas taxicolor) sex identification based on amelogenin gene - Ming Zhou; Jiaojiao Yu; Rui Xue; Biao Li; Jiandong Yang (Conservation Genetics Resources, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Graphene oxide wrapped copper-benzene-1,3,5-tricarboxylate metal organic framework as efficient absorbent for gaseous toluene under ambient conditions - Yexin Dai; Meng Li; Fang Liu; Ming Xue; Yongqiang Wang; Chaocheng Zhao (Environmental Science and Pollution Research, 2019)

Altered intrinsic brain activity and memory performance improvement in patients with end-stage renal disease during a single dialysis session - Peng Li; Dun Ding; Xue-ying Ma; Hua-wen Zhang; Ji-xin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Seasonal and Spatial Variability of Water Quality and Nutrient Removal Efficiency of Restored Wetland: A Case Study in Fujin National Wetland Park, China - Nan Li; Xue Tian; Yu Li; Hongchen Fu; Xueying Jia; Guangze Jin; Ming Jiang (Chinese Geographical Science, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

Dynamic changes in energy metabolism and electron transport of photosystem II in Nicotiana tabacum infested by nymphs of Bemisia tabaci (Middle East-Asia Minor 1) - Qingliang Li; Wei Tan; Ming Xue; Haipeng Zhao (Arthropod-Plant Interactions, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29 - Li Ma; Shuai Chao Zheng; Ti Kun Zhang; Zi Yi Liu; Xue Jian Wang; Xing Kui Zhou; Cheng Gang Yang; Jin Ling Duo; Ming He Mo (Antonie van Leeuwenhoek, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Wideband dipole logging based on segment linear frequency modulation excitation - Xue-Shen Cao; Hao Chen; Ping Li; Hong-Bin He; Yin-Qiu Zhou; Xiu-Ming Wang (Applied Geophysics, 2018)

Toxic effect and mechanism of four ionic liquids on seedling taproots of Arabidopsis thaliana - Ming Li; Yonglai Xue; Zhenjiang Liu; Jin Guo; Liyun Liu; Yuanyuan Zhang; Lu Gao; Lizhao Wang; Yin Cui; Daolin Du (Environmental Science and Pollution Research, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

A Highly Selective Naphthalimide-Based Chemosensor: “Naked-Eye” Colorimetric and Fluorescent Turn-On Recognition of Al3+ and Its Application in Practical Samples, Test Paper and Logic Gate - Na-Na Li; Shuang Zeng; Ming-Qiang Li; Yu-Qing Ma; Xue-Jiao Sun; Zhi-Yong Xing; Jin-Long Li (Journal of Fluorescence, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

A risk management system for meteorological disasters of solar greenhouse vegetables - Ming Li; Sining Chen; Fang Liu; Li Zhao; Qingyu Xue; Hui Wang; Meixiang Chen; Peng Lei; Dongmei Wen; Jorge Antonio Sanchez-Molina; Jose Fernando Bienvenido; Zhenfa Li; et al. (Precision Agriculture, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Abnormal structure and functional connectivity of the anterior insula at pain-free periovulation is associated with perceived pain during menstruation - Wang-huan Dun; Jing Yang; Ling Yang; Dun Ding; Xue-ying Ma; Feng-Li Liang; Karen M. von Deneen; Shao-hui Ma; Xiao-ling Xu; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2017)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Electrophysiologic Studies on the Risks and Potential Mechanism Underlying the Proarrhythmic Nature of Azithromycin - Mengdan Zhang; Ming Xie; Sha Li; Ying Gao; Shuyin Xue; Huili Huang; Kesu Chen; Fuming Liu; Long Chen (Cardiovascular Toxicology, 2017)

Identification and Characterization of microRNAs from Saccharum officinarum L by Deep Sequencing - Aijuan Xue; Zhen Li; Muchen Cai; Qing Zhang; Xingtan Zhang; Ray Ming; Jisen Zhang (Tropical Plant Biology, 2017)

Antioxidants Attenuate Acute and Chronic Itch: Peripheral and Central Mechanisms of Oxidative Stress in Pruritus - Feng-Ming Zhou; Ruo-Xiao Cheng; Shuai Wang; Ya Huang; Yong-Jing Gao; Yan Zhou; Teng-Teng Liu; Xue-Long Wang; Li-Hua Chen; Tong Liu (Neuroscience Bulletin, 2017)

Resveratrol Inhibits Diabetic-Induced Müller Cells Apoptosis through MicroRNA-29b/Specificity Protein 1 Pathway - Kaihong Zeng; Yuan Wang; Na Yang; Duozi Wang; Suping Li; Jian Ming; Jing Wang; Xuemei Yu; Yi Song; Xue Zhou; Bo Deng; Xiaona Wu; et al. (Molecular Neurobiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Serratia bozhouensis sp. nov., Isolated from Sewage Samples of a Dairy Farm - Fei Shang; Ting Xue; Man Wang; Xiaolin Chen; Li Yu; Ming Zhang (Current Microbiology, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

The septin protein S ep4 facilitates host infection by plant fungal pathogens via mediating initiation of infection structure formation - Hui‐Qiang Feng; Gui‐Hua Li; Shun‐Wen Du; Song Yang; Xue‐Qian Li; Paul de Figueiredo; Qing‐Ming Qin (Environmental Microbiology, 2017)
Summary Many phytopathogenic fungi use infection structures (IFSs, i.e., appressoria and infection cushions) to penetrate host cuticles. However, the conserved mechanisms that mediate initiation of IFS formation in divergent pathogens upon sensing the presence of host plants remain obscure. Here, we demonstrate that a conserved septin gene SEP4 plays crucial roles in this process. Disruption of SEP4 in the plant grey mould fungus Botrytis cinerea completely blocked IFS formation and abolished the virulence of Δ Bcsep4 mutants on unwounded hosts. During IFS formation, mutants lacking SEP4 could produce reactive oxygen species (ROS) normally. Inhibition of ROS production in strains harbouring the SEP4 gene resulted in disordered assembly of Sep4 and the subsequent failure to form infection cushions, suggesting that proper Sep4 assembly regulated by ROS is required for initiation of IFS formation and infection. Moreover, loss of SEP4 severely impaired mutant conidiation, melanin and chitin accumulation in hyphal tips and lesion expansion on wounded hosts, but significantly promoted germ tube elongation and sclerotium production. SEP4 ‐mediated fungal pathogenic development, including IFS formation, was validated in the hemibiotroph Magnaporthe oryzae . Our findings indicate that Sep4 plays pleiotropic roles in B. cinerea development and specifically facilities host infection by mediating initiation of IFS formation in divergent plant fungal pathogens in response to ROS signaling.

Altered Amygdala Resting-State Functional Connectivity in Maintenance Hemodialysis End-Stage Renal Disease Patients with Depressive Mood - Hui Juan Chen; Yun Fei Wang; Rongfeng Qi; U. Joseph Schoepf; Akos Varga-Szemes; B. Devon Ball; Zhe Zhang; Xiang Kong; Jiqiu Wen; Xue Li; Guang Ming Lu; Long Jiang Zhang (Molecular Neurobiology, 2017)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Spatial characteristics of extreme rainfall over China with hourly through 24-hour accumulation periods based on national-level hourly rain gauge data - Yongguang Zheng; Ming Xue; Bo Li; Jiong Chen; Zuyu Tao (Advances in Atmospheric Sciences, 2016)
Hourly rainfall measurements of 1919 national-level meteorological stations from 1981 through 2012 are used to document, for the first time, the climatology of extreme rainfall in hourly through 24-h accumulation periods in China. Rainfall amounts for 3-, 6-, 12- and 24-h periods at each station are constructed through running accumulation from hourly rainfall data that have been screened by proper quality control procedures. For each station and for each accumulation period, the historical maximum is found, and the corresponding 50-year return values are estimated using generalized extreme value theory. Based on the percentiles of the two types of extreme rainfall values among all the stations, standard thresholds separating Grade I, Grade II and Grade III extreme rainfall are established, which roughly correspond to the 70th and 90th percentiles for each of the accumulation periods. The spatial characteristics of the two types of extreme rainfall are then examined for different accumulation periods. The spatial distributions of extreme rainfall in hourly through 6-h periods are more similar than those of 12- and 24-h periods. Grade III rainfall is mostly found over South China, the western Sichuan Basin, along the southern and eastern coastlines, and in the large river basins and plains. There are similar numbers of stations with Grade III extreme hourly rainfall north and south of 30°N, but the percentage increases to about 70% south of 30°N as the accumulation period increases to 24 hours, reflecting richer moisture and more prolonged rain events in southern China. Potential applications of the extreme rainfall climatology and classification standards are suggested at the end.

Recent significant tornadoes in China - Ming Xue; Kun Zhao; Mingjung Wang; Zhaohui Li; Yongguang Zheng (Advances in Atmospheric Sciences, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

The Formation of Barrier Winds East of the Loess Plateau and Their Effects on Dispersion Conditions in the North China Plains - Xiao-Ming Hu; Xingliang Li; Ming Xue; Dui Wu; Jose D. Fuentes (Boundary-Layer Meteorology, 2016)

Soil nitrate–N residue, loss and accumulation affected by soil surface management and precipitation in a winter wheat-summer fallow system on dryland - Gang He; Zhaohui Wang; Fucui Li; Jian Dai; Xiaolong Ma; Qiang Li; Cheng Xue; Hanbing Cao; Sen Wang; Hui Liu; Laichao Luo; Ming Huang; et al. (Nutrient Cycling in Agroecosystems, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Impaired SIRT1 promotes the migration of vascular smooth muscle cell-derived foam cells - Ming-Jie Zhang; Yi Zhou; Lei Chen; Xu Wang; Yan Pi; Chun-Yan Long; Meng-Jiao Sun; Xue Chen; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Neuroprotective Effects of β-Asarone Against 6-Hydroxy Dopamine-Induced Parkinsonism via JNK/Bcl-2/Beclin-1 Pathway - Sheng Zhang; Xue-Hong Gui; Li-Ping Huang; Min-Zhen Deng; Ruo-Ming Fang; Xue-Hong Ke; Yu-Ping He; Ling Li; Yong-Qi Fang (Molecular Neurobiology, 2016)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

Orientation selectivity in cat primary visual cortex: local and global measurement - Tao Xu; Hong-Mei Yan; Xue-Mei Song; Ming Li (Neuroscience Bulletin, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

The impact of hemodialysis on cognitive dysfunction in patients with end-stage renal disease: a resting-state functional MRI study - Hui Juan Chen; Rongfeng Qi; Xiang Kong; Jiqiu Wen; Xue Liang; Zhe Zhang; Xue Li; Guang Ming Lu; Long Jiang Zhang (Metabolic Brain Disease, 2015)

Outbreak of Edwardsiella tarda infection in farm-cultured giant mottled eel Anguilla marmorata in China - Ze-Quan Mo; Ling Zhou; Xiang Zhang; Lian Gan; Li Liu; Xue-Ming Dan (Fisheries Science, 2015)

Proteome analysis of pear reveals key genes associated with fruit development and quality - Jia Ming Li; Xiao San Huang; Lie Ting Li; Dan Man Zheng; Cheng Xue; Shao Ling Zhang; Jun Wu (Planta, 2015)

Preparation and Characterization of a Novel Extracellular Polysaccharide with Antioxidant Activity, from the Mangrove-Associated Fungus Fusarium oxysporum - Yan-Li Chen; Wen-Jun Mao; Hong-Wen Tao; Wei-Ming Zhu; Meng-Xia Yan; Xue Liu; Tian-Tian Guo; Tao Guo (Marine Biotechnology, 2015)

ACE2 and Ang-(1–7) protect endothelial cell function and prevent early atherosclerosis by inhibiting inflammatory response - Yue-Hui Zhang; Yong-huan Zhang; Xue-Fei Dong; Qing-Qing Hao; Xiao-Ming Zhou; Qing-Tao Yu; Shu-Ying Li; Xu Chen; Abdulai Fallah Tengbeh; Bo Dong; Yun Zhang (Inflammation Research, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Systematic discovery and characterization of stress-related microRNA genes in Oryza sativa - Kai Bin Xie; Xue Zhou; Tian Hai Zhang; Bao Long Zhang; Li Ming Chen; Guo Xiang Chen (Biologia, 2015)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Assessment of carbon sustainability under different tillage systems in a double rice cropping system in Southern China - Jian-Fu Xue; Sheng-Li Liu; Zhong-Du Chen; Fu Chen; Rattan Lal; Hai-Ming Tang; Hai-Lin Zhang (The International Journal of Life Cycle Assessment, 2014)

Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) prevents apoptosis induced by hydrogen peroxide in basilar artery smooth muscle cells - Jia-Wei Zeng; Xue-Lin Zeng; Fei-Ya Li; Ming-Ming Ma; Feng Yuan; Jie Liu; Xiao-Fei Lv; Guan-Lei Wang; Yong-Yuan Guan (Apoptosis, 2014)

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System - Fengxia Guo; Xiaohong Li; Juan Peng; Yaling Tang; Qin Yang; Lushan Liu; Zuo Wang; Zhisheng Jiang; Ming Xiao; Chuyu Ni; Ruixing Chen; Dangheng Wei; et al. (Annals of Biomedical Engineering, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Molecular modeling studies of JNK3 inhibitors using QSAR and docking - Xiang-Xiang Wu; Da-Shun Dai; Xin Zhu; Xiao-Fei Li; Juan Yuan; Xue-Fen Wu; Ming-San Miao; Hua-Hui Zeng; Chun-Lei Zhao (Medicinal Chemistry Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Long-term activity of earthquake-induced landslides: A case study from Qionghai Lake Basin, Southwest of China - Xue-li Wei; Ning-sheng Chen; Qian-gong Cheng; Na He; Ming-feng Deng; Javed Iqbal Tanoli (Journal of Mountain Science, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Shuang Liang; Xue-lai Wang; Ming-yang Zou; Han Wang; Xue Zhou; Cai-hong Sun; Wei Xia; Li-jie Wu; Takashi X. Fujisawa; Akemi Tomoda (Journal of Zhejiang University-SCIENCE B, 2014)

Epigallocatechin-3-gallate induces apoptosis, inhibits proliferation and decreases invasion of glioma cell - Hong Li; Zhe Li; Ya-Ming Xu; Yue Wu; Kang-Kang Yu; Can Zhang; Yong-Hua Ji; Gang Ding; Fu-Xue Chen (Neuroscience Bulletin, 2014)

Improvement of a gene targeting system for genetic manipulation in Penicillium digitatum - Qian Xu; Cong-yi Zhu; Ming-shang Wang; Xue-peng Sun; Hong-ye Li (Journal of Zhejiang University-SCIENCE B, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Characterization of novel polymorphic microsatellite markers from the cDNA library of Japanese scallop Mizuhopecten yessoensis and cross-species amplification in bay scallop Argopecten irradians - XIANG YING MENG; XIU LI WANG; XIAO LI GUO; MENG CHEN; YING MING ZHANG; HONG YUE WANG; YA QING CHANG; XUE MEI QIU (Journal of Genetics, 2013)

Proteomic analysis of apoptotic and oncotic pancreatic acinar AR42J cells treated with caerulein - Jiangtao Chu; Hongliang Ji; Ming Lu; Zhituo Li; Xin Qiao; Bei Sun; Weihui Zhang; Dongbo Xue (Molecular and Cellular Biochemistry, 2013)

Treatment of Furfural Residue by Solvent Extraction for Enzymatic Hydrolysis: Effect of Delignification on the Structure and Digestibility - Shao-Ni Sun; Xue-Fei Cao; Ming-Fei Li; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Dynamic changes in photosynthesis and chlorophyll fluorescence in Nicotiana tabacum infested by Bemisia tabaci (Middle East–Asia Minor 1) nymphs - Qingliang Li; Wei Tan; Ming Xue; Haipeng Zhao; Chenxiang Wang (Arthropod-Plant Interactions, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

Amyloid plaque pathogenesis in 5XFAD mouse spinal cord: retrograde transneuronal modulation after peripheral nerve injury - Jian-Ming Li; Zhi-Qin Xue; Si-Hao Deng; Xue-Gang Luo; Peter R. Patrylo; Gregory W. Rose; Huaibin Cai; Yan Cai; Xiao-Xin Yan (Neurotoxicity Research, 2013)

LPS induces cardiomyocyte injury through calcium-sensing receptor - Hong-yu Wang; Xue-yan Liu; Gan Han; Zhu-ying Wang; Xiao-xie Li; Zhi-mei Jiang; Chun-ming Jiang (Molecular and Cellular Biochemistry, 2013)

Short-chain chlorinated paraffins (SCCPs) in surface soil from a background area in China: occurrence, distribution, and congener profiles - Xue-Tong Wang; Yuan Zhang; Yi Miao; Ling-Ling Ma; Yuan-Cheng Li; Yue-Ya Chang; Ming-Hong Wu (Environmental Science and Pollution Research, 2013)

Identification of Major QTL for Waterlogging Tolerance Using Genome-Wide Association and Linkage Mapping of Maize Seedlings - Xiaobo Zhang; Bin Tang; Feng Yu; Liu Li; Ming Wang; Yadong Xue; Zuxin Zhang; Jianbing Yan; Bing Yue; Yonglian Zheng; Fazhan Qiu (Plant Molecular Biology Reporter, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

Biochemical characterization of NADP+-dependent isocitrate dehydrogenase from Microcystis aeruginosa PCC7806 - Ming-Ming Jin; Peng Wang; Xue Li; Xiao-Yu Zhao; Lei Xu; Ping Song; Guo-Ping Zhu (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Bioactive alkaloids produced by Pseudomonas brassicacearum subsp. Neoaurantiaca, an endophytic bacterium from Salvia miltiorrhiza - Xiao-Jun Li; Hao-Yu Tang; Jia-Li Duan; Jin-Ming Gao; Quan-Hong Xue (Natural Product Research, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Comparative study of the contents of analogues of aristolochic acid in two kinds of Aristolochiae Fructus by high-performance liquid chromatography - Yu-Qiong Xu; Xiao-Wei Li; Guang-Xue Liu; Xuan Wang; Ming-Ying Shang; Xiao-Mei Li; Shao-Qing Cai (Journal of Natural Medicines, 2013)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Metabolomic study of serum from rabbits with acute acalculous cholecystitis - Zhituo Li; Huaishu Shen; Yingmei Zhang; Ming Lu; Xin Qiao; Xianzhi Meng; Bei Sun; Dongbo Xue; Weihui Zhang (Inflammation Research, 2012)

Use of multi-electrode array recordings in studies of network synaptic plasticity in both time and space - Ming-Gang Liu; Xue-Feng Chen; Ting He; Zhen Li; Jun Chen (Neuroscience Bulletin, 2012)

Disruption of the Gene Encoding β-1, 3-Glucanase in Marine-Derived Williopsis saturnus WC91-2 Enhances its Killer Toxin Activity - Jin-Li Xu; Xue Zhang; Huai-Yong Sun; Zhen-Ming Chi (Marine Biotechnology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Effect of Simultaneously Replacing Putative TM6 and TM12 of Human NBCe1-A with Those from NBCn1 on Surface Abundance in Xenopus Oocytes - Li-Ming Chen; Xue Qin; Fraser J. Moss; Ying Liu; Walter F. Boron (The Journal of Membrane Biology, 2012)

Differential expression of AdipoR1, IGFBP3, PPARγ and correlative genes during porcine preadipocyte differentiation - Hai-Feng Liu; Ming-Xing Gui; Han Dong; Xun Wang; Xue-Wei Li (In Vitro Cellular & Developmental Biology - Animal, 2012)

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

A risk-associated single nucleotide polymorphism of SMAD7 is common to colorectal, gastric, and lung cancers in a Han Chinese population - Xin Li; Xue-xi Yang; Ni-ya Hu; Jing-zhe Sun; Fen-xia Li; Ming Li (Molecular Biology Reports, 2011)

The AGL6-like Gene CpAGL6, a Potential Regulator of Floral Time and Organ Identity in Wintersweet (Chimonanthus praecox) - Bei-Guo Wang; Qiong Zhang; Li-Gang Wang; Ke Duan; Ai-Hu Pan; Xue-Ming Tang; Shun-Zhao Sui; Ming-Yang Li (Journal of Plant Growth Regulation, 2011)

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Ds-echinoside A, a new triterpene glycoside derived from sea cucumber, exhibits antimetastatic activity via the inhibition of NF-κB-dependent MMP-9 and VEGF expressions - Qin Zhao; Zhi-dong Liu; Yong Xue; Jing-feng Wang; Hui Li; Qing-juan Tang; Yu-ming Wang; Ping Dong; Chang-hu Xue (Journal of Zhejiang University-SCIENCE B, 2011)

Comparison of cardioprotective and anti-inflammatory effects of ischemia pre- and postconditioning in rats with myocardial ischemia–reperfusion injury - Jun Xiong; Qiang Wang; Fu-Shan Xue; Yuan-Jing Yuan; Shan Li; Jian-Hua Liu; Xu Liao; Yan-Ming Zhang (Inflammation Research, 2011)

Alkaline-stress response in Glycine soja leaf identifies specific transcription factors and ABA-mediated signaling factors - Ying Ge; Yong Li; De-Kang Lv; Xi Bai; Wei Ji; Hua Cai; Ao-Xue Wang; Yan-Ming Zhu (Functional & Integrative Genomics, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Influence of 14-day hind limb unloading on isolated muscle spindle activity in rats - Xue Hong Zhao; Xiao Li Fan; Xin Ai Song; Su Di Wu; Jun Chan Ren; Ming Xia Chen (Journal of Muscle Research and Cell Motility, 2010)

Induction and origin of adventitious roots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Shi-Jie Chai; Li-Ping Chen; Ming-Fang Zhang; Jing-Quan Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Responses of two rice cultivars differing in seedling-stage nitrogen use efficiency to growth under low-nitrogen conditions - Wei Ming Shi; Wei Feng Xu; Su Mei Li; Xue Qiang Zhao; Gang Qiang Dong (Plant and Soil, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Allograft rejection-related gene expression in the endothelial cells of renal transplantation recipients after cytomegalovirus infection - Yang Li; Hang Yan; Wu-jun Xue; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; Xin-shun Feng; Xiao-hui Tian; He-li Xiang; Jun Hou (Journal of Zhejiang University-SCIENCE B, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

FAS −1,377 G/A polymorphism is associated with cancer susceptibility: evidence from 10,564 cases and 12,075 controls - Li-Xin Qiu; Jian Shi; Hui Yuan; Xin Jiang; Kai Xue; Hai-Feng Pan; Jin Li; Ming-Hua Zheng (Human Genetics, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Ambient air monitoring of Beijing MSW logistics facilities in 2006 - Chun-Ping Li; Guo-Xue Li; Yi-Ming Luo; Yan-Fu Li (Environmental Monitoring and Assessment, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Development of thirteen microsatellite loci for Impatiens lateristachys (Balsaminaceae) - Lin-Feng Li; Guo-Qing Chen; Yong-Ming Yuan; Xue-Jun Ge (Conservation Genetics, 2008)

Purification and characterization of a thermostable uricase from Microbacterium sp. strain ZZJ4-1 - Lei Kai; Xiao-Hang Ma; Xue-Lai Zhou; Xiao-Ming Jia; Xia Li; Kang-Ping Guo (World Journal of Microbiology and Biotechnology, 2008)

Identification of functional candidate genes for drought tolerance in rice - Bin-Ying Fu; Jian-Hua Xiong; Ling-Hua Zhu; Xiu-Qin Zhao; Hua-Xue Xu; Yong-Ming Gao; Yang-Sheng Li; Jian-Long Xu; Zhi-Kang Li (Molecular Genetics and Genomics, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

The panorama of the diversity of H5 subtype influenza viruses - Hong-Chao Ma; Ji-Ming Chen; Ji-Wang Chen; Ying-Xue Sun; Jin-Ming Li; Zhi-Liang Wang (Virus Genes, 2007)

A preliminary panorama of the diversity of N1 subtype influenza viruses - Ji-Ming Chen; Hong-Chao Ma; Ji-Wang Chen; Ying-Xue Sun; Jin-Ming Li; Zhi-Liang Wang (Virus Genes, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

Reduction in the in vitro expression of Brain–Pancreas Relative Protein by oxygen and glucose-deprivation - Yan-Hua Lin; Ai-Hua Liu; Yan Pan; Christel Westenbroek; Gert J Ter Horst; He-Ming Yu; Xue-Jun Li (Molecular and Cellular Biochemistry, 2007)

Improved production of ethanol by deleting FPS1 and over-expressing GLT1 in Saccharomyces cerevisiae - Qing-Xue Kong; Ji-Guang Gu; Li-Min Cao; Ai-Li Zhang; Xun Chen; Xue-Ming Zhao (Biotechnology Letters, 2006)

A stable and differentiable RNA positive control for reverse transcription-polymerase chain reaction - Ji-Ming Chen; Li-Xia Guo; Cheng-Ying Sun; Ying-Xue Sun; Ji-Wang Chen; Lin Li; Zhi-Liang Wang (Biotechnology Letters, 2006)

Artificial synthesis of interspecific chimeras between tuber mustard (Brassica juncea) and cabbage (Brassica oleracea) and cytological analysis - Li-Ping Chen; Ya-Ming Ge; Xue-Yun Zhu (Plant Cell Reports, 2006)

In situ and in vitro colonization of Cathaya argyrophylla (Pinaceae) by ectomycorrhizal fungi - Lu-Min Vaario; Shu-Tang Xing; Zong-Qiang Xie; Zhi-Ming Lun; Xue Sun; Yu Hua Li (Mycorrhiza, 2006)

Direct somatic embryogenesis induced from cotyledons of mango immature zygotic embryos - Jie-Ning Xiao; Xue-Lin Huang; Yong-Jie Wu; Xiao-Ju Li; Ming-De Zhou; Florent Engelmann (In Vitro Cellular & Developmental Biology - Plant, 2004)

Fed-batch fermentation of Lactobacillus lactis for hyper-production of l-lactic acid - Dong-Mei Bai; Qiang Wei; Zhi-Hui Yan; Xue-Ming Zhao; Xin-Gang Li; Shi-Min Xu (Biotechnology Letters, 2003)